Quantum dots, production method thereof, electronic device including the same

KR103020798B1Active Publication Date: 2026-09-16SAMSUNG ELECTRONICS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020210138855
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-16
Filing Date
2021-10-18
Publication Date
2026-09-16
Estimated Expiration
2041-10-18

Smart Images

  • Figure 112021119240521-PAT00001_ABST
    Figure 112021119240521-PAT00001_ABST
Patent Text Reader

Abstract

The invention relates to a non-cadmium quantum dot comprising a core including a first semiconductor nanocrystal including zinc, tellurium, and selenium, and a semiconductor nanocrystal shell disposed on the core including zinc chalcogenide, further including magnesium, and having a Te / Se molar ratio of 0.1 or higher, a method for manufacturing the same, and an electronic device including the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The invention relates to quantum dots, a method for manufacturing the same, and a composite or electronic device (display device) containing the same. Background Technology

[0002] Unlike bulk materials, nanoparticles can control physical properties (such as energy bandgap and melting point), which are known as intrinsic material characteristics, based on their particle size. For example, semiconductor nanocrystalline particles, also known as quantum dots, are crystalline materials of several nanometers in size. Due to their extremely small size, they have a large surface area per unit volume and exhibit quantum confinement effects, allowing them to display physical properties different from those of bulk materials of the same composition. Quantum dots absorb light from an excitation source to enter an excited energy state and emit energy corresponding to their energy bandgap. The problem to be solved

[0003] One embodiment relates to an eco-friendly quantum dot capable of realizing improved optical properties (e.g., luminescence efficiency).

[0004] Another embodiment relates to a method for manufacturing the aforementioned quantum dots.

[0005] Another embodiment relates to a quantum dot complex comprising the aforementioned quantum dots.

[0006] Another embodiment relates to an electronic device (e.g., a display device) comprising the aforementioned quantum dots. means of solving the problem

[0007] Quantum dot(s) of one embodiment (hereinafter also referred to as quantum dots) comprise zinc, tellurium, and selenium. The quantum dots may have a core-shell structure comprising a core comprising a first semiconductor nanocrystal comprising zinc, tellurium, and selenium, and a semiconductor nanocrystal shell disposed on the core comprising zinc chalcogenide. The quantum dots further comprise magnesium, the molar ratio of tellurium to selenium in the quantum dots is 0.1 or greater, and the quantum dots do not comprise cadmium.

[0008] The above quantum dots can be configured to emit green light.

[0009] The maximum emission peak of the green light or the quantum dot may exist in a wavelength range of 480 nm or more and 580 nm or less. The wavelength of the maximum emission peak may be 490 nm or more, 500 nm or more, 510 nm or more, or 520 nm or more. The wavelength of the maximum emission peak may be 560 nm or less, 550 nm or less, or 545 nm or less.

[0010] The above quantum dots may not contain lead, mercury, or a combination thereof.

[0011] The first semiconductor nanocrystal or the core may include a first zinc chalcogenide comprising zinc, tellurium, and selenium.

[0012] In the above quantum dots, the molar ratio of tellurium to selenium (Te / Se) may be 0.15 or more, 0.2 or more, 0.25 or more, 0.3 or more, or 0.32 or more.

[0013] In the above quantum dots, the molar ratio of magnesium to zinc may be 0.01 or more, 0.1 or more, or 0.2 or more. In the above quantum dots, the molar ratio of magnesium to zinc may be 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.5 or less.

[0014] In the above quantum dots, the molar ratio of magnesium to tellurium may be 0.001 or more, 0.01 or more, 0.1 or more, 0.5 or more, 1 or more, 1.5 or more, 2 or more, 3 or more, or 3.2 or more.

[0015] In the above quantum dots, the molar ratio of magnesium to tellurium may be 10 or less, 7 or less, 6 or less, 5.7 or less, 5 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, or 2 or less.

[0016] The above quantum dot may contain magnesium in the core, the semiconductor nanocrystal shell, or at the interface between the core and the semiconductor nanocrystal shell. In the quantum dot, magnesium may be present in the semiconductor nanocrystal shell.

[0017] The core (or the quantum dot) may not include semiconductor nanocrystals comprising a group III-V compound (e.g., indium phosphide, gallium phosphide, indium zinc phosphide, or a combination thereof).

[0018] The above quantum dots may not contain indium, gallium, or a combination thereof.

[0019] The above quantum dots may be water-insoluble.

[0020] The first semiconductor nanocrystal above is ZnTe x Se 1-x (Here, x is 0.15 or greater, 0.4 or greater, or 0.5 or greater and 0.95 or less, or 0.9 or less) may be included.

[0021] In the core or the first semiconductor nanocrystal, the molar ratio of tellurium to selenium may be 0.15 or more, 0.2 or more, 0.3 or more, 0.4 or more, or 0.5 or more. In the core or the first semiconductor nanocrystal, the molar ratio of tellurium to selenium may be 5 or less, 4 or less, 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, or 0.7 or less.

[0022] The above quantum dot (or the above semiconductor nanocrystal shell) comprises selenium and sulfur, and the molar ratio of sulfur to selenium in the above quantum dot may be greater than 0, 0.01 or more, 0.02 or more, 0.05 or more, 0.1 or more, 0.13 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 1 or more, 1.5 or more, or 2 or more. In the above quantum dot, the molar ratio of sulfur to selenium may be 8 or less, 6 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, or 0.55 or less.

[0023] The molar ratio of the total amount of sulfur and selenium to tellurium in the above quantum dots may be less than 15, 14 or less, 13 or less, 12 or less, 11 or less, or 10.5 or less.

[0024] The above quantum dots may have a molar ratio of sulfur to zinc of 0.95 or less, 0.6 or less, 0.56 or less, 0.4 or less, 0.3 or less, or 0.2 or less.

[0025] The above quantum dots may have a molar ratio of tellurium to sulfur (Te / S) of 0.1 or more, 0.12 or more, 0.13 or more, 0.15 or more, or 0.2 or more. The above quantum dots may have a molar ratio of tellurium to sulfur (Te / S) of 2 or less.

[0026] The above quantum dots may further include an additional metal comprising an alkali metal, aluminum, or a combination thereof. The alkali metal may include lithium. In the above quantum dots, the molar ratio of the additional metal to tellurium may be 0.001 or more, 0.01 or more, or 0.05 or more. In the above quantum dots, the molar ratio of the additional metal to tellurium may be 10 or less, or 8 or less, 7 or less, or 6 or less. The above quantum dots may further include aluminum. In the above quantum dots, the molar ratio of aluminum to tellurium (Al / Te) may be 0.005 or more or 0.5 or less.

[0027] The maximum emission peak of the above quantum dot may have a full width at half maximum of 45 nm or less, 43 nm or less, 40 nm or less, 39 nm or less, 38 nm or less, or 37 nm or less.

[0028] The above quantum dots may have a quantum efficiency of 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, or 80% or more.

[0029] The above quantum dots may include organic ligands (e.g., coordinated to the surface).

[0030] The above organic ligand may include RCOOH, RNH2, R2NH, R3N, RSH, RH2PO, R2HPO, R3PO, RH2P, R2HP, R3P, ROH, RCOOR', RPO(OH)2, RHPOOH, R2POOH (wherein R and R' are each independently a substituted or unsubstituted C1 to C40 aliphatic hydrocarbon, or a substituted or unsubstituted C6 to C40 aromatic hydrocarbon), a polymer organic ligand, or a combination thereof.

[0031] The above quantum dots may have an (average) size of 4.5 nm or more, or 4.8 nm or more. The above quantum dots may have an (average) size of 7 nm or less, 6.5 nm or less, 6 nm or less, or 5.5 nm or less.

[0032] The semiconductor nanocrystal shell may include a first shell layer disposed on the core and a second shell layer disposed on the first shell layer.

[0033] The first shell layer comprises a second semiconductor nanocrystal, and the second shell layer may comprise a third semiconductor nanocrystal having a composition different from that of the second semiconductor nanocrystal. The second shell layer may be the outermost layer.

[0034] The second semiconductor nanocrystal may include zinc, selenium, and optionally sulfur. The second semiconductor nanocrystal may or may not include sulfur. The third semiconductor nanocrystal may include zinc and sulfur. The third semiconductor nanocrystal may or may not include selenium. At least one of the second semiconductor nanocrystal and the third semiconductor nanocrystal may further include magnesium.

[0035] The second semiconductor nanocrystal may include zinc selenide and optionally magnesium selenide. The third semiconductor nanocrystal may include zinc sulfide and optionally magnesium sulfide.

[0036] The above quantum dots may not show metallic magnesium or magnesium oxide peaks when verified by XPS.

[0037] In another embodiment, the method for manufacturing the aforementioned quantum dots is,

[0038] A step of preparing a core particle including the above core;

[0039] The method comprises the step of forming the semiconductor nanocrystal shell on the surface of the core particle by reacting the zinc precursor and the chalcogen element precursor at a shell-forming temperature in the presence of the core particle and the first organic ligand in a first organic solvent.

[0040] It includes adding a magnesium precursor to the reaction system in at least one of the steps of preparing the core particles and forming the semiconductor nanocrystal shell.

[0041] The step of preparing the core particles may include reacting a zinc precursor, a selenium precursor, and a tellurium precursor at a core formation temperature. The preparation of the core comprises the step of preparing a zinc precursor organic solution comprising a zinc precursor and a second organic ligand in a second organic solvent;

[0042] It may include adding a selenium precursor, a tellurium precursor, a hydride compound (e.g., a hydride compound comprising lithium, aluminum, or a combination thereof), and a third organic ligand different from the second organic ligand simultaneously or sequentially while heating the zinc precursor organic solution to a core forming temperature.

[0043] The magnesium precursor may include magnesium carboxylate, magnesium alkylate, or a combination thereof.

[0044] In another embodiment, the quantum dot complex comprises a matrix (e.g., a polymer matrix); and a plurality of quantum dots dispersed within the matrix, and

[0045] The plurality of quantum dots mentioned above may include the aforementioned quantum dot(s).

[0046] The above matrix may include a polymer.

[0047] The above matrix may include a crosslinked polymer, a binder having carboxylic acid groups (monomer or polymer), or a combination thereof.

[0048] The cross-linked polymer may include a polymerization product of a photopolymerizable monomer containing a carbon-carbon double bond, a polymerization product between the photopolymerizable monomer and a multi-thiol compound having at least two thiol groups at the ends, or a combination thereof.

[0049] The above quantum dot complex may further include metal oxide microparticles dispersed within the matrix.

[0050] In another embodiment, the display element comprises a light-emitting element and, optionally, a light source, wherein the photoluminescent element comprises the aforementioned quantum dot or the aforementioned quantum dot complex, and, if present, the light source is configured to provide incident light to the light-emitting element.

[0051] The incident light may have a maximum peak wavelength in the range of 440 nm to 560 nm or 445 nm (or 450 nm) to 460 nm.

[0052] The above-mentioned light-emitting element may include a sheet of the above-mentioned quantum dot complex.

[0053] The light-emitting element may be a stacked structure comprising a substrate and a photoluminescent layer disposed on the substrate. The photoluminescent layer may include a pattern of the quantum dot complex. The pattern may include one or more repeating sections that emit light of a predetermined wavelength.

[0054] The above display element can be configured to have a color reproduction rate of 80% or more under the BT2020 standard.

[0055] In another embodiment, the electronic device comprises a first electrode and a second electrode facing each other; and an active layer located between the first electrode and the second electrode and including the aforementioned quantum dots.

[0056] The above electronic device may further include a charge assist layer (e.g., a hole assist layer) disposed between the first electrode and the active layer.

[0057] It may further include a charge auxiliary layer (e.g., an electronic auxiliary layer) disposed between the second electrode and the active layer.

[0058] The quantum dots of the first embodiment can emit light of a desired wavelength (e.g., greater than 470 nm or green) with improved optical properties (e.g., improved efficiency with reduced full width at half maximum) while substantially not containing harmful heavy metals such as cadmium. Effects of the invention

[0059] The quantum dots of one embodiment can be used in the light-emitting layer of various display devices (e.g., photoluminescent or electroluminescent display devices) and can contribute to the realization of high color reproduction and high-efficiency displays. The quantum dots of one embodiment can also be used as light-emitting materials in biomolecular fluorescent labels, security inks, etc., and can increase the number of colors distinguishable in the visible light region. The quantum dots of one embodiment can also be utilized in high-sensitivity optical sensors. Brief explanation of the drawing

[0060] Figure 1 is a schematic diagram showing the cross-sectional structure and band alignment of a quantum dot according to a non-limiting embodiment. FIG. 2a schematically illustrates a pattern formation process using a composition of one embodiment. FIG. 2b schematically illustrates a pattern formation process using an ink composition of one embodiment. Figure 3 shows an exploded view of a display element according to one embodiment. FIGS. 4a and FIGS. 4b show schematic cross-sectional views of a display element according to one embodiment. FIG. 5 shows a schematic cross-sectional view of a display element according to one embodiment. FIG. 6a shows a schematic cross-sectional view of a light-emitting element according to one embodiment. FIG. 6b shows a schematic cross-sectional view of a light-emitting element according to one embodiment. FIG. 6c shows a schematic cross-sectional view of a light-emitting element according to one embodiment. Figure 7 shows the TEM EDX analysis results of the quantum dots prepared in Example 1. Specific details for implementing the invention

[0061] The advantages and features of the technology described below, and the methods for achieving them, will become clear by referring to the embodiments described below in detail together with the accompanying drawings. However, the forms of implementation are not limited to the embodiments disclosed below. Unless otherwise defined, all terms used in this specification (including technical and scientific terms) may be used in a meaning that is commonly understood by those skilled in the art. Furthermore, terms defined in commonly used dictionaries are not to be interpreted ideally or excessively unless explicitly and specifically defined otherwise. Throughout the specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.

[0062] In addition, the singular form includes the plural form unless specifically mentioned otherwise in the phrase.

[0063] Thicknesses have been enlarged in the drawings to clearly represent various layers and regions. Throughout the specification, the same reference numerals have been used for similar parts.

[0064] When a part such as a layer, membrane, region, or plate is said to be "on" another part, this includes not only the case where it is "directly on" another part, but also the case where there is another part in between. Conversely, when a part is said to be "directly on" another part, it means that there is no other part in between.

[0065] Unless otherwise defined below, "substitution" means that a compound or its residue, instead of hydrogen, comprises a C1 to C30 alkyl group, a C2 to C30 alkenyl group, a C2 to C30 alkynyl group, a C6 to C30 aryl group, a C7 to C30 alkylaryl group, a C1 to C30 alkoxy group, a C1 to C30 heteroalkyl group, a C3 to C30 heteroalkylaryl group, a C3 to C30 cycloalkyl group, a C3 to C15 cycloalkenyl group, a C6 to C30 cycloalkynyl group, a C2 to C30 heterocycloalkyl group, a halogen (-F, -Cl, -Br, or -I), a hydroxyl group (-OH), a nitro group (-NO2), a cyano group (-CN), an amino group (-NRR', where R and R' are independently hydrogen or a C1 to C6 alkyl group), It means substituted with a substituent selected from an azido group (-N3), an amidino group (-C(=NH)NH2)), a hydrazino group (-NHNH2), a hydrazono group (-N(NH2)), an aldehyde group (-C(=O)H), a carbamoyl group (-C(O)NH2), a thiol group (-SH), an ester group (-C(=O)OR, where R is a C1 to C6 alkyl group or a C6 to C12 aryl group), a carboxyl group (-COOH) or its salt (-C(=O)OM, where M is an organic or inorganic cation), a sulfonic acid group (-SO3H) or its salt (-SO3M, where M is an organic or inorganic cation), a phosphate group (-PO3H2) or its salt (-PO3MH or -PO3M2, where M is an organic or inorganic cation) and combinations thereof.

[0066] Herein, the term hydrocarbon group refers to a group containing carbon and hydrogen (e.g., alkyl, alkenyl, alkynyl, or aryl groups, etc.). The hydrocarbon group may be a monovalent or higher group formed by the removal of one or more hydrogen atoms from an alkane, alkene, alkyne, or arene. In the hydrocarbon group, one or more methylenes may be replaced by oxide residues, carbonyl residues, ester residues, -NH-, or a combination thereof.

[0067] Here, "aromatic" means an organic compound or organic group comprising one or more unsaturated ring groups having delocalized pi electrons.

[0068] Here, "aliphatic" may be a saturated or unsaturated, linear or branched hydrocarbon group. The aliphatic group may be an alkyl, alkenyl, or alkynyl group.

[0069] Here, alkyl refers to a linear or branched saturated monovalent hydrocarbon group (methyl, ethylhexyl, etc.). Here, alkenyl refers to a linear or branched monovalent hydrocarbon group having one or more carbon-carbon double bonds. Here, alkynyl refers to a linear or branched monovalent hydrocarbon group having one or more carbon-carbon triple bonds.

[0070] Here, "aryl" means a group formed by the removal of one or more hydrogens from an aromatic group (e.g., a phenyl or naphthyl group). Here, "hetero" means comprising one to three heteroatoms which may be N, O, S, Si, P, or a combination thereof.

[0071] In this specification, "Group" refers to a group of the periodic table of elements.

[0072] "Group III" may include Group IIIA and Group IIIB, and examples of Group III metals include but are not limited to In, Ga, and Tl. "Group V" includes Group V and includes but is not limited to nitrogen, phosphorus, arsenic, antimony, and bismuth.

[0073] Here, the mean can be the median or the mean. In one embodiment, the mean can be the mean.

[0074] Here, quantum efficiency can be relative or absolute quantum yield, which can be easily measured by commercially available equipment (e.g., from Hitachi or Hamamatsu Corporation). Quantum efficiency (or quantum yield) can be measured in a solution state or in a solid state (within a composite). In one embodiment, quantum efficiency (or quantum yield) is the ratio of emitted photons to photons absorbed by a nanostructure or a group thereof. In one embodiment, quantum efficiency can be measured by any method. For example, for fluorescence quantum yield or efficiency, there may be two methods: the absolute method and the relative method.

[0075] In the absolute method, the quantum efficiency is obtained by detecting the fluorescence of all samples through an integrating sphere. In the relative method, the quantum efficiency of an unknown sample is calculated by comparing the fluorescence intensity of a standard dye (standard sample) with the fluorescence intensity of an unknown sample. Coumarin 153, Coumarin 545, Rhodamine 101 inner salt, Anthracene, and Rhodamine 6G, among others, may be used as standard dyes depending on their PL wavelengths, but are not limited thereto.

[0076] QY or quantum efficiency can be easily and reproducibly determined by using commercially available equipment from companies such as Hitachi Co. Ltd or Hamamatsu Co. Ltd and by referring to manuals provided by the equipment manufacturers.

[0077] The full width at half maximum and the maximum PL peak wavelength can be measured by the photoluminescence spectrum obtained by a spectrophotometer, such as a fluorescence spectrophotometer, for example.

[0078] Here, the description that it does not contain cadmium (or other specific elements) may refer to the content of cadmium (or specific elements) being 0.1 wt%, 0.01 wt%, 0.005 wt% or less, 0.001 wt% or less, 100 ppm or less, 50 ppm or less, 10 ppm or less, or nearly 0, based on the total elements of the quantum dots. In one embodiment, the quantum dots are substantially free of cadmium (or harmful heavy metals), or even if present, are present in an amount below the detection limit of a given detection means or at an impurity level.

[0079] Semiconductor nanocrystalline particles (hereinafter also referred to as quantum dots) can absorb light from an excitation source and emit light corresponding to their energy bandgap. The energy bandgap of quantum dots can vary depending on the size and / or composition of the nanocrystals. For example, as the size of a quantum dot increases, it may have a narrower energy bandgap and an increased wavelength of emission. Semiconductor nanocrystals are attracting attention as light-emitting materials in various fields, such as display devices, energy devices, and bioluminescent devices.

[0080] Many quantum dots possessing luminescence properties suitable for practical applications are based on hazardous heavy metals such as cadmium (Cd), lead (Pb), and / or mercury (Hg). Hazardous heavy metals like cadmium pose serious environmental and health issues and are regulated elements under the Restriction of Hazardous Substances (RoHS) directive in many countries. Therefore, there is a need to develop environmentally friendly quantum dots capable of emitting light of desired wavelengths while possessing enhanced luminescence characteristics (e.g., when applied to electroluminescent devices). Among these quantum dots, InP-based QDs are known to be applicable to actual devices.

[0081] Meanwhile, to realize a display with high color reproduction rate under the next-generation standard BT2020 for quantum dot displays (e.g., where the color conversion layer contains quantum dots), it may be required that the quantum dots have a reduced full width at half maximum (FWHM). To achieve improved color reproduction rate under the BT2020 standard, it may be required that the light-emitting material have a reduced FWHM. However, quantum dots based on III-V group compounds containing indium (In) and phosphorus (P) have smaller band gaps and larger Bohr radii compared to cadmium-based cores such as CdSe cores, resulting in a significant variation in FWHM with respect to size. InP-based quantum dots find it difficult to exhibit a reduced FWHM while emitting light at desired wavelengths (e.g., greater than 470 nm, greater than 475 nm, greater than 480 nm, and less than 580 nm). Cores containing indium and phosphorus are susceptible to surface oxidation, which can increase the FWHM upon shell coating, making it difficult to simultaneously achieve the desired levels of quantum efficiency and FWHM.

[0082] As confirmed by the inventors, as cadmium-free quantum dots, ZnTeSe-based quantum dots have a narrower bandgap change with respect to particle size change compared to indium phosphide-based quantum dots or cadmium-based quantum dots. In other words, even when there is a large change in particle size, the change in the emission wavelength of the quantum dot can be limited, which can be advantageous for realizing a reduced full width at half maximum.

[0083] However, as confirmed by the inventors, it is difficult for a ZnTeSe-based core to exhibit desired luminescence characteristics in a structure coated with an inorganic shell (particularly zinc chalcogenide).

[0084] Although not intended to be bound by any specific theory, when a zinc chalcogenide (e.g., ZnSe and / or ZnS) semiconductor nanocrystal shell is placed on a ZnTeSe core, the difference in conduction band offset between the core and the shell is insufficient. Therefore, it may be difficult to obtain the desired level of high quantum efficiency, even with the provision of a shell layer of improved quality. Furthermore, as confirmed by the inventors, when a ZnSe-based shell is formed on a core having an increased tellurium content, there is a problem of the emission wavelength of the core being significantly red-shifted, which may make it more difficult to design quantum dots to emit light of the desired wavelength.

[0085] According to one embodiment, a quantum dot emitting light of a desired wavelength while exhibiting enhanced luminescence properties can be obtained by introducing magnesium (e.g., during shell formation). Although not intended to be bound by any specific theory, the introduction of magnesium as described below is thought to enable the control of energy band properties between the core and the shell (band gap engineering, increase in conduction band offset). Furthermore, a ZnTeSe core containing an increased amount of tellurium (e.g., ZnTe x Se 1-xIt was confirmed that providing a zinc selenide-based shell with magnesium introduced together with the core (where x is 0.1 to 1 or less, or 0.6 to 0.67) can suppress the red shift of the core wavelength to a limited level. Although not bound by any specific theory, it is believed that the introduction of magnesium increases the band offset between the core and shell as described above, while minimizing the lattice strain between them. Consequently, the electron confinement effect is increased for the entire quantum dot, which can lower the possibility of defect formation on the quantum dot surface and improve the optical properties (e.g., quantum efficiency) and stability of the final ZnTeSe QD. Since the red shift of the emission wavelength occurring during the shell coating process is suppressed due to the introduction of magnesium, it is thought that a shell thicker than 1 ml can be formed while exhibiting an emission wavelength in the green region (especially, PL peak wavelength ~530 nm). In summary, the quantum dot according to one embodiment can emit light of a desired wavelength (e.g., green light) while having enhanced optical properties and not containing harmful heavy metals such as cadmium, lead, or mercury.

[0086] The quantum dot of one embodiment comprises zinc, tellurium, and selenium. The quantum dot has a core-shell structure. The core-shell structure comprises a core comprising a first semiconductor nanocrystal and a semiconductor nanocrystal shell disposed on the core (e.g., at least a portion of the surface of the core) and comprising zinc chalcogenide. The quantum dot further comprises magnesium.

[0087] The above quantum dots may contain a predetermined range of tellurium (e.g., in the core). For example, the first semiconductor nanocrystal or the core may contain a first zinc chalcogenide comprising zinc, tellurium, and selenium. The content of each component in the quantum dots described herein can be confirmed through appropriate analytical means (e.g., inductively coupled plasma atomic emission spectroscopy (ICP-AES), X-ray photoelectron spectroscopy (XPS), ion chromatography, transmission electron microscopy energy-dispersive X-ray spectroscopy (TEM-EDS), etc.).

[0088] The core may include a first zinc chalcogenide crystal (e.g., a zinc compound containing selenium and tellurium in an alloy or doping form). In the core, the telluride content may be in excess of the selenium. In the semiconductor nanocrystal shell, the second zinc chalcogenide has a different composition from the first zinc chalcogenide and may include zinc and one or more chalcogen elements selected from selenium, sulfur, and tellurium.

[0089] In the quantum dots of the first embodiment, the first semiconductor nanocrystal included in the core is ZnTe x Se 1-x(where, x is greater than 0.1, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.51 or more, 0.52 or more, 0.53 or more, 0.54 or more, 0.55 or more, 0.56 or more, 0.57 or more, 0.58 or more, 0.59 or more, 0.6 or more, 0.61 or more, 0.62 or more, 0.63 or more, 0.64 or more, 0.65 or more, 0.66 or more, 0.67 or more, 0.68 or more, 0.69 or more, 0.70 or more, 0.71 or more, 0.72 or more, 0.73 or more, 0.74 or more, or 0.75 or more and 0.95 or less, 0.89 or less, 0.88 or less, 0.87 or less, 0.86 or less, It may include 0.85 or less, 0.84 or less, 0.83 or less, 0.82 or less, 0.8 or less, 0.75 or less, 0.74 or less, 0.73 or less, 0.72 or less, 0.71 or less, 0.7 or less, 0.69 or less, 0.68 or less, 0.67 or less, 0.66 or less, 0.65 or less, 0.5 or less, 0.4 or less, 0.3 or less, or 0.2 or less.

[0090] In the quantum dots of one embodiment, the ratio of the molar content of tellurium to selenium (Te / Se) is 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, 0.27 or more, 0.3 or more, 0.31 or more, 0.35 or more, 0.4 or more, 0.45 or more, 0.5 or more, 0.55 or more, 0.6 or more, 0.65 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, 0.93 or more, 0.95 or more, 1 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, 2 or more, 2.1 or more, 2.2 or more, 2.3 It may be 2.4 or more, 2.5 or more, 2.6 or more, 2.7 or more, 2.8 or more, 2.9 or more, or 3 or more.

[0091] In the quantum dots of one embodiment, the molar ratio of tellurium to selenium (Te / Se) may be 4 or less, 3.9 or less, 3.8 or less, 3.7 or less, 3.6 or less, 3.5 or less, 3.4 or less, 3.3 or less, 3.2 or less, 3.1 or less, 3 or less, 2.9 or less, 2.8 or less, 2.7 or less, 2.6 or less, 2.5 or less, 2.4 or less, 2.3 or less, 2.2 or less, 2.1 or less, 2.0 or less, 1.9 or less, 1.8 or less, 1.7 or less, 1.6 or less, 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, 1.1 or less, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, or 0.6 or less.

[0092] In the above quantum dots or in the above core (or first semiconductor nanocrystal) , The molar ratio of selenium (Se / Te) to tellurium may be 7 or less, 6.5 or less, 6 or less, 5.5 or less, 5 or less, 4.5 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, or 0.45 or less.

[0093] In the above quantum dots or in the above core (or first semiconductor nanocrystal) , The molar ratio of selenium (Se / Te) to tellurium may be 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, 0.3 or more, 0.35 or more, 0.4 or more, 0.5 or more, 0.55 or more, 0.6 or more, 0.65 or more, 0.67 or more, 0.7 or more, 0.75 or more, 0.8 or more, 0.85 or more, 0.9 or more, 0.95 or more, 1 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, 1.5 or more, 1.6 or more, 1.7 or more, 1.8 or more, 1.9 or more, 2 or more, 2.5 or more, 3 or more, 3.5 or more, 4 or more, 4.5 or more, 5 or more, or 5.5 or more.

[0094] In the quantum dots of one embodiment, the molar ratio of tellurium to zinc (Te / Zn) may be greater than 0.03, greater than 0.04, greater than 0.045, greater than 0.05, greater than 0.06, greater than 0.9, greater than 0.1, greater than 0.15, greater than 0.2, greater than 0.25, greater than 0.3, greater than 0.35, greater than 0.4, or greater than 0.43. In the quantum dots of one embodiment, the molar ratio of tellurium to zinc (Te / Zn) (e.g., when measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES)) may be less than 1, e.g., 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.3 or less, 0.25 or less, 0.2 or less, 0.15 or less, or 0.1 or less.

[0095] In the quantum dots of one embodiment, the Zn content relative to Te (Zn / Te) may be 0.5 or more, 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, 10 or more, or 15 or more. The Zn content relative to Te (Zn / Te) may be 40 or less, 35 or less, 30 or less, 25 or less, 20 or less, 17 or less, 15 or less, 10 or less, 9 or less, 8.5 or less, 8 or less, 7.5 or less, 7 or less, 6.5 or less, 6 or less, 5.5 or less, 4.5 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2.4 or less, 2.3 or less, or 2.25 or less.

[0096] The quantum dots of one embodiment may further include sulfur, and if present, the molar ratio of sulfur to zinc may be 0.005 or more, 0.01 or more, 0.015 or more, 0.02 or more, 0.025 or more, 0.03 or more, 0.035 or more, 0.04 or more, 0.045 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, 0.1 or more, 0.15 or more, 0.2 or more, 0.25 or more, 0.3 or more, or 0.35 or more and 0.95 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less.

[0097] In the quantum dots of the first embodiment, the molar ratio of sulfur to tellurium (S / Te) is, It may be 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 1 or more, 3 or more, 5 or more, 6 or more, 7 or more, 9 or more, or 10 or more and 20 or less, 18 or less, 16 or less, 14 or less, 12 or less, 10 or less, 6 or less, 5 or less, 4.5 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, 0.9 or less, 0.8 or less, 0.7 or less, 0.6 or less, 0.5 or less, or 0.4 or less.

[0098] In the quantum dots of one embodiment, the molar ratio of the total sum of sulfur and selenium to tellurium may be 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, 8 or more, 9 or more, or 10 or more. In the quantum dots of one embodiment, the molar ratio of the total sum of sulfur and selenium to tellurium may be 16 or less, 15 or less, 14 or less, 13 or less, 12 or less, 11 or less, 10 or less, 9 or less, 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or 2 or less.

[0099] The above quantum dots (e.g., the core and / or the shell) may not contain manganese, copper, or a combination thereof. The above quantum dots may not contain a Group III-V compound. The above Group III-V compound may include indium phosphide, indium zinc phosphide, gallium phosphide, or a combination thereof.

[0100] The above quantum dots may not exhibit peaks corresponding to crystals of the above III-V group compounds (e.g., indium phosphide or gallium phosphide) in X-ray diffraction analysis. The above quantum dots may not contain indium, gallium, or a combination thereof.

[0101] The quantum dot of one embodiment further comprises magnesium (e.g., the core, the interface between the core and the semiconductor nanocrystal shell, and / or the semiconductor nanocrystal shell). In the manufacturing method described below, magnesium can be introduced into the quantum dot by adding a magnesium precursor during the process of forming the core and / or shell.

[0102] In the quantum dots of one embodiment, the magnesium content is 0.001 mole or more, 0.005 mole or more, 0.01 mole or more, 0.05 mole or more, 0.1 mole or more, 0.15 mole or more, 0.2 mole or more, 0.25 mole or more, 0.3 mole or more, 0.35 mole or more, 0.4 mole or more, 0.45 mole or more, 0.5 mole or more, 0.55 mole or more, 0.6 mole or more, 0.65 mole or more, 0.7 mole or more, 0.75 mole or more, 0.8 mole or more, 0.85 mole or more, 0.9 mole or more, 0.95 mole or more, 1 mole or more, 1.1 mole or more, 1.2 mole or more, 1.3 mole or more, 1.4 mole or more, 1.5 mole or more, 1.6 mole or more, 1.7 mole or more, per mole of tellurium. It may be 1.8 moles or more, 1.9 moles or more, 2 moles or more, 2.1 moles or more, 2.2 moles or more, 2.3 moles or more, 2.4 moles or more, 2.5 moles or more, 2.6 moles or more, 2.7 moles or more, 2.8 moles or more, 2.9 moles or more, 3.1 moles or more, 3.2 moles or more, 3.3 moles or more, 3.4 moles or more, 3.5 moles or more, 3.6 moles or more, 3.7 moles or more, 3.8 moles or more, 3.9 moles or more, or 4 moles or more.

[0103] In the quantum dots of one embodiment, the magnesium content may be 10 moles or less, 9 moles or less, 8 moles or less, 7 moles or less, 6.5 moles or less, 6 moles or less, 5.5 moles or less, 5 moles or less, 4.5 moles or less, 4 moles or less, 3.9 moles or less, 3.8 moles or less, 3.7 moles or less, 3.6 moles or less, 3.5 moles or less, 3 moles or less, 2.5 moles or less, or 2 moles or less per mole of tellurium.

[0104] In the quantum point of one embodiment, the magnesium content (atomic ratio) to zinc (e.g., confirmed by XPS) may be 0.01 or higher, 0.05 or higher, 0.1 or higher, 0.15 or higher, or 0.2 or higher. In the quantum point of one embodiment, the magnesium content (atomic ratio) to zinc (e.g., confirmed by XPS) may be 1 or lower, 0.7 or lower, 0.5 or lower, 0.4 or lower, or 0.3 or lower.

[0105] The above quantum dots may further include an alkali metal, aluminum, or a combination thereof as an additional metal. The alkali metal may include lithium, sodium, potassium, cesium, rubidium, or a combination thereof. The alkali metal may include lithium. In the above quantum dots, the content of the additional metal may be 0.005 or more, 0.01 or more, 0.05 or more, 0.1 or more, 0.2 or more, 0.3 or more, 0.4 or more, 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, 0.9 or more, or 1 or more per mole of tellurium. In the above quantum dots, the content of additional metal may be 10 or less, 9.5 or less, 9 or less, 8.5 or less, 8 or less, 7.5 or less, 7 or less, 6.5 or less, 6 or less, 5.5 or less, 5 or less, 4.5 or less, 4 or less, 3.5 or less, 3 or less, 2.5 or less, 2 or less, 1.5 or less, 1 or less, 0.9 or less, 0.85 or less, 0.8 or less, 0.75 or less, 0.7 or less, 0.65 or less, 0.6 or less, or 0.55 or less per mole of tellurium.

[0106] The shell may be a multilayer shell comprising a plurality of layers. The adjacent shell layers among the plurality of layers may comprise semiconductor materials having different compositions. The multilayer shell may comprise a first layer disposed immediately above the core and a second layer disposed above the first layer. The first layer may comprise the second semiconductor nanocrystal. The second layer may comprise a third semiconductor nanocrystal having a composition different from that of the second semiconductor nanocrystal. The second shell layer may be the outermost layer of a quantum dot.

[0107] The semiconductor nanocrystal shell may further include magnesium. The semiconductor nanocrystal shell is Zn 1-y (Mg) y Se z S 1-zIt may include. (here, 0 <y<1, 0≤z≤1). y 또는 z 는 0.1-0.9, 0.2-0.8, 0.3-0.7, 0.4-0.6, 또는 이들의 조합일 수 있다.

[0108] Referring to FIG. 1, the quantum dot of one embodiment may have a magnesium-containing zinc selenide (e.g., magnesium-rich zinc selenide) in the first layer. In one embodiment, the magnesium-rich zinc selenide is ZnTe x Se 1-x It can be placed directly on top of the core. In a quantum dot of one embodiment, zinc selenide with a changed magnesium concentration may be provided on the semiconductor nanocrystal shell (e.g., the first shell layer). Although not intended to be bound by any specific theory, the magnesium-containing zinc selenide may have lattice parameters similar to those of a ZnTeSe-containing core containing a relatively increased amount of tellurium or capable of emitting green light, and may provide a desirable band offset in energy band alignment, which may be advantageous for electron confinement of the final quantum dot. Accordingly, the red shift phenomenon occurring during shell coating may be mitigated, allowing for the provision of a shell with increased thickness. If the second layer contains Mg, the difference in lattice constants between the first and second layers may be further reduced, and improvements in quantum efficiency and stability may be achieved due to reduced strain occurring at the junction interface of heterogeneous shell materials and the resulting reduction in the probability of defect formation.

[0109] Referring to Fig. 1, Zn (1-y) Mg y Se shell layer and / or Zn (1-y') Mg y'An S shell layer may be disposed on a ZnTeSe core. In one embodiment, y and y' are 0 - 1, 0.1 - 0.9, 0.2 - 0.8, 0.3 - 0.7, 0.4 - 0.6, or a combination thereof. In one embodiment, y, y', or both thereof may be greater than 0 and less than 1.

[0110] The first shell layer or the second semiconductor nanocrystal may comprise zinc, selenium, and optionally sulfur. The second shell layer or the third semiconductor nanocrystal may comprise zinc and sulfur. The third semiconductor nanocrystal may not comprise selenium. In one embodiment, the first shell layer may comprise ZnSe, ZnSeS, ZnS, or a combination thereof. The second shell layer may be composed of ZnS.

[0111] At least one of the second semiconductor nanocrystal and the third semiconductor nanocrystal (e.g., the second semiconductor nanocrystal, the third semiconductor nanocrystal, or the second semiconductor nanocrystal and the third semiconductor nanocrystal) may further include magnesium. At least one of the second semiconductor nanocrystal and the third semiconductor nanocrystal may include ZnMgSe, ZnMgS, ZnMgSeS, or a combination thereof.

[0112] In the case of a multilayer shell, the thickness of each layer can be appropriately selected. In one embodiment, the first shell layer and the second shell layer may each independently be 1 monolayer or more, e.g., 2 ml or more, 3 ml or more, 4 ml or more, 5 ml or more, and 10 ml or less, e.g., 9 ml or less, 8 ml or less, 7 ml or less, 6 ml or less, or 5 ml or less. In a multilayer shell, the thickness of each layer can be determined by taking into account the composition of the entire quantum dot.

[0113] The total shell thickness may be 1 monolayer or more, e.g., 2 ml or more, 3 ml or more, 4 ml or more, 5 ml or more, and 20 ml or less, e.g., 19 ml or less, 18 ml or less, 17 ml or less, 16 ml or less, 15 ml or less, 14 ml or less, 13 ml or less, 12 ml or less, 11 ml or less, 10 ml or less, 9 ml or less, 8 ml or less, 7 ml or less, 6 ml or less, 5 ml or less, or 4 ml or less.

[0114] In the above shell or multilayer shell, each layer may be a gradient alloy having a composition that changes in the radial direction. In one embodiment, the sulfur content within the semiconductor nanocrystal shell may increase toward the surface of the quantum dot. For example, in the shell, the sulfur content may have a concentration gradient that increases as it moves away from the core.

[0115] In the quantum dots of one embodiment, the size of the core(s) (e.g., average size) may be 1 nm or more, e.g., 2 nm or more, 2.5 nm or more, 3 nm or more, 3.5 nm or more, 4 nm or more, or 4.5 nm or more. The size of the core (e.g., average size) may be 7 nm or less, 6 nm or less, 5 nm or less, 4 nm or less, 3 nm or less, or 2 nm or less.

[0116] The (average) size of the quantum dot(s) of one embodiment may be 2 nm or more, 3 nm or more, 4 nm or more, 5 nm or more, 6 nm or more, 7 nm or more, 7.5 nm or more, 8 nm or more, 8.5 nm or more, 9 nm or more, 9.5 nm or more, or 10 nm or more. The (average) particle size of the quantum dot(s) of one embodiment may be 50 nm or less, for example, 45 nm or less, 40 nm or less, 35 nm or less, 30 nm or less, 25 nm or less, 24 nm or less, 23 nm or less, 22 nm or less, 21 nm or less, 20 nm or less, 19 nm or less, 18 nm or less, 17 nm or less, 16 nm or less, 15 nm or less, 14 nm or less, 13 nm or less, 12 nm or less, 11 nm or less, 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6.5 nm or less, 6 nm or less, 5.5 nm or less, or 5 nm or less. Here, the size of the quantum dot may refer to the diameter (or, if not spherical, the diameter calculated by assuming it is spherical from the electron microscope two-dimensional image of the quantum dot). Here, size may refer to the size of a single quantum dot or the average size of a group of quantum dots. The size of the quantum dot can be obtained, for example, by using an image analysis program (e.g., imageJ) on a transmission electron microscope image. Here, the mean may be the mean or the median.

[0117] The aforementioned quantum dots may form a quantum dot group. The group of the aforementioned quantum dots may have a standard deviation of size of less than 18% of the average size, for example, 17% or less, 16% or less, 15% or less, 14% or less, 13% or less, 12% or less, or 11% or less. The group of the aforementioned quantum dots may have a standard deviation of size of 8% or more, 9% or more, or 10% or more of the average size.

[0118] In a non-limiting embodiment, the quantum dot may have a valley that is relatively clearly identifiable in the UV absorption spectrum of (e.g., core or core-shell).

[0119] In a non-limiting embodiment, the quantum dot may have a valley that is relatively clearly identifiable in the UV absorption spectrum of (e.g., core or core-shell).

[0120] In one embodiment, the quantum dots may have a valley in the UV-Vis absorption spectrum, for example, adjacent to the first absorption peak, or at a range of 450 nm or more (or 440 nm or more, 430 nm or more, 420 nm or more, 410 nm or more, or 400 nm or more) and the wavelength of the first absorption peak.

[0121] The quantum dot of one embodiment may exhibit a valley depth greater than a predetermined value in the UV-Vis absorption spectrum. The valley or its lowest point has a wavelength lower than the first absorption peak. In the UV-Vis absorption spectrum of the quantum dot of one embodiment, the intensity of the first absorption peak is greater than the intensity at the lowest point of the valley adjacent to the first absorption peak. Although not intended to be bound by any specific theory, the presence of a valley or valley depth (VD) in the absorption spectrum of the quantum dot may suggest improvements in size distribution and coating quality. The fact that the absorption spectrum of the quantum dot or core quantum dot exhibits an identifiable VD may suggest that the quantum dot or core has an improved size distribution and / or improved coating quality. Improved coating quality may lead to a narrower full width at half maximum and increased luminescence efficiency.

[0122] In the quantum dots of one embodiment, the validation depth defined as follows may be 0.01 or greater, e.g., 0.02 or greater, 0.03 or greater, 0.04 or greater, 0.05 or greater, 0.06 or greater, 0.07 or greater, 0.08 or greater, 0.09 or greater, or 0.1 or greater:

[0123] (Absfirst - Abs valley ) / Abs first = VD

[0124] Abs first : Absorption at the wavelength of the first absorption peak

[0125] Abs valley : Absorption at the lowest point of the valley.

[0126] The first absorption peak of the above quantum dot may exist in a wavelength region of 410 nm or more, for example, 420 nm or more, 430 nm or more, 440 nm or more, 450 nm or more, 460 nm or more, 465 nm or more, 470 nm or more, 475 nm or more, 480 nm or more.

[0127] The lowest point of the valley of the above quantum dot may exist in a wavelength region of 410 nm or more, for example, 420 nm or more, 430 nm or more, 440 nm or more, 450 nm or more, 460 nm or more, 465 nm or more, 470 nm or more, 475 nm or more, 480 nm or more.

[0128] The first absorption peak or the lowest point of the valley may exist at wavelengths of 530 nm or less, 525 nm or less, 520 nm or less, 515 nm or less, 510 nm or less, 505 nm or less, 500 nm or less, 495 nm or less, 490 nm or less, 485 nm or less, 480 nm or less, 475 nm or less, 465 nm or less, 460 nm or less, 455 nm or less, 450 nm or less, and 445 nm or less.

[0129] The above quantum dot may emit green light. The above quantum dot may have a maximum photoluminescence peak in a wavelength region of 480 nm or more, 485 nm or more, 490 nm or more, 495 nm or more, 500 nm or more, 505 nm or more, 510 nm or more, 515 nm or more, or 520 nm or more. The above quantum dot may have a maximum photoluminescence peak in a wavelength region of 580 nm or less, 570 nm or less, 560 nm or less, 550 nm or less, 540 nm or less, or 535 nm or less. Within the aforementioned range, the green light may have a maximum emission peak wavelength of 500 nm to 560 nm (e.g., 515 nm or more and 535 nm or less).

[0130] The quantum dots of one embodiment can exhibit significantly improved (photoluminescent) quantum efficiency (e.g., 60% or more) compared to known quantum dots based on Zn, Se, and Te. Quantum efficiency is the ratio of emitted photons to photons absorbed by the quantum dot(s). Quantum efficiency can be measured by a comparison method using a well-characterized standard sample with a known quantum yield value, or by absolute measurement using an integrating sphere. Quantum efficiency measuring devices are commercially available from various manufacturers (e.g., Hitachi or Hamamatsu).

[0131] The quantum dot of the first embodiment can exhibit a quantum efficiency of 60% or more, 65% or more, 70% or more, 75% or more, or 80% or more (in photoluminescence analysis). The quantum efficiency may be 100% or less.

[0132] The quantum dot of one embodiment may have a full width at half maximum (in photoluminescence analysis) of 45 nm or less, 40 nm or less, 39 nm or less, 38 nm or less, 37 nm or less, 36 nm or less, 35 nm or less, e.g., 34 nm or less, 33 nm or less, 32 nm or less, 31 nm or less, 30 nm or less, 29 nm or less, 28 nm or less, 27 nm or less, 26 nm or less, or 25 nm or less. The full width at half maximum may be 1 nm or more, 5 nm or more, 10 nm or more, or 15 nm or more.

[0133] The above quantum dot may include an organic ligand on its surface. The organic ligand may include RCOOH, RNH2, R2NH, R3N, RSH, RH2PO, R2HPO, R3PO, RH2P, R2HP, R3P, ROH, RCOOR', RPO(OH)2, RHPOOH, R2POOH (wherein R and R' each independently include a C1 to C40 (e.g., C3 to C30 or C6 to C24) substituted or unsubstituted aliphatic hydrocarbon, or a C6 to C40 substituted or unsubstituted aromatic hydrocarbon, or a combination thereof), or a combination thereof. The organic ligand may include alone or a mixture of two or more compounds.

[0134] Specific examples of the above organic ligand compounds include methanethiol, ethanethiol, propanethiol, butanethiol, pentanthiol, hexanethiol, octanethiol, dodecanethiol, hexadecanethiol, octadecanethiol, benzylthiol; methaneamine, ethaneamine, propaneamine, butaneamine, pentanamine, hexaneamine, octaneamine, dodecaneamine, hexadecylamine, oleylamine, octadecylamine, dimethylamine, diethylamine, dipropylamine; methanoic acid, ethanoic acid, propanoic acid, butanoic acid, pentanic acid, hexanoic acid, heptanoic acid, octanoic acid, dodecanoic acid, hexadecanoic acid, octadecanic acid, oleic acid, benzoic acid, palmitic acid, stearic acid; Phosphines such as methylphosphine, ethylphosphine, propylphosphine, butylphosphine, pentylphosphine, tributylphosphine, trioctylphosphine, etc.; phosphine compounds such as methylphosphine oxide, ethylphosphine oxide, propylphosphine oxide, butylphosphine oxide, trioctylphosphine oxide, etc., or their oxide compounds; diphenylphosphine, triphenylphosphine compounds or their oxide compounds; phosphonic acids, etc., may be examples, but are not limited thereto. . The above organic ligand compound can be used alone or as a mixture of two or more.

[0135] In one embodiment, the organic ligand compound may be a combination of RCOOH and an amine (e.g., RNH2, R2NH, and / or R3N).

[0136] The above organic ligand may not include a compound having both a carboxylic acid group and a thiol group. The above organic ligand may not include glutathione. The above quantum dot may be water insoluble.

[0137] The above quantum dots may exhibit an average particle size of 300 nm or more, 400 nm or more, 500 nm or more, or 900 nm or more in dynamic light scattering analysis when dispersed in water. The above quantum dots may be dispersed in an organic solvent to form a quantum dot organic solution having an average particle size of 500 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, or 100 nm or less in dynamic light scattering analysis. The organic solvent is as described below.

[0138] In another embodiment, the above-described method for manufacturing quantum dots is,

[0139] A step of preparing a particle comprising a core including a first semiconductor nanocrystal including zinc, selenium, and tellurium;

[0140] The method comprises the step of performing a shell-forming reaction between a zinc precursor and a chalcogen element precursor in a first organic solvent at a shell-forming temperature in the presence of the core and a first organic ligand to form a semiconductor nanocrystal shell containing zinc chalcogenide on the surface of a particle containing the core.

[0141] A magnesium precursor is added to the reaction system in at least one of the steps of preparing the core particles and forming the semiconductor nanocrystal shell.

[0142] In the step of preparing the core, the formation of a ZnTeSe-containing nanocrystal may include preparing a zinc precursor organic solution containing a zinc precursor and a second organic ligand in a second organic solvent, and performing a core formation reaction by adding the selenium precursor, tellurium precursor, hydride compound, and at least one third organic ligand to the zinc precursor organic solution while heating it to a core formation reaction temperature.

[0143] The core forming temperature may be 250°C or higher, 260°C or higher, 270°C or higher, 280°C or higher, 290°C or higher, or 300°C or higher. The first reaction temperature may be 280°C or higher. The core forming temperature may be 350°C or lower, for example, 340°C or lower, 330°C or lower, 320°C or lower, or 310°C or lower. The reaction time for core formation can be appropriately selected taking into account the precursors for core formation, the reaction temperature, and the desired core size.

[0144] The synthesized core can be separated from the reaction system (e.g., before the shell formation step) (e.g., by the addition of a non-solvent). The separation of the non-solvent will be described separately later.

[0145] Detailed information regarding the composition of the quantum dots, the core, and the semiconductor nanocrystal shell is as described above.

[0146] In the method of one embodiment, the tellurium precursor during core synthesis comprises tellurium dispersed in an organic solvent, and the tellurium concentration in the tellurium precursor may be greater than 0.1 M, e.g., 0.5 M or more, or greater than 0.5 M, 1 M or more, 1.5 M or more, 2 M or more, or 2.5 M or more. When such tellurium concentrations are used, the reactivity of the tellurium precursor may be improved, and a core of improved quality may be provided.

[0147] When synthesizing the core, the tellurium precursor, the metal hydride compound, and the third organic ligand may be mixed as a single stock solution at a temperature below 80°C, for example, 75°C or lower, 70°C or lower, 65°C or lower, 60°C or lower, 55°C or lower, 50°C or lower, or 45°C or lower, before addition to the zinc precursor organic solution. The temperature may be 10°C or higher, 20°C or higher, or room temperature.

[0148] The third organic ligand may include an aliphatic organic amine or a combination thereof.

[0149] The metal hydride compound may include lithium, aluminum, or a combination thereof. The metal hydride compound may include aluminum hydride, lithium hydride, or a combination thereof. The metal hydride compound may include an organometallic hydride compound (e.g., having one or more hydrocarbon groups), an inorganic metal hydride compound, or a combination thereof. The metal hydride compound may include an alkyl lithium hydride (e.g., a dialkyl lithium borohydride in which the alkyl group has 1 to 10 carbons), a lithium aluminum hydride compound, or a combination thereof.

[0150] The amount of metal hydride compound used is not particularly limited and can be appropriately selected. The metal hydride content may be 0.01 mole or more, 0.05 mole or more, 0.1 mole or more, 0.5 mole or more, or 1 mole or more per mole of tellurium. The metal hydride content may be 10 moles or less, 5 moles or less, or 3 moles or less per mole of tellurium.

[0151] In the step of preparing the core, the molar ratio of tellurium to selenium introduced into the reaction system (Te / Se) may be greater than 0.25, greater than 0.3, greater than 0.4, greater than 0.5, greater than 0.7, greater than 0.9, greater than 1, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, greater than 1.6, greater than 1.7, greater than 1.8, greater than 1.9, greater than 2, or greater than 2.5. In the step of preparing the core, the molar ratio of tellurium to selenium introduced into the reaction system (Te / Se) may be less than 10, less than 9, less than 8, less than 7, less than 6, less than 5, less than 4, less than 3, less than 2, or less than 1.5.

[0152] In the step of preparing the core, the molar ratio of zinc to tellurium introduced into the reaction system can be appropriately determined by considering precursors, etc., to obtain a desired composition. For example, in the step of preparing the core, the molar ratio of zinc to 1 mole of tellurium introduced into the reaction system may be 1 mole or more, 2 moles or more, 3 moles or more, 4 moles or more, or 5 moles or more. In the step of preparing the core, the molar ratio of zinc to 1 mole of tellurium introduced into the reaction system may be 20 moles or less, 15 moles or less, 10 moles or less, 9 moles or less, 8 moles or less, 7 moles or less, 6 moles or less, 5 moles or less, 4 moles or less, 3 moles or less, or 2 moles or less.

[0153] In one embodiment, the shell forming step involves heating (or vacuuming) the first organic solvent and the first organic ligand under vacuum to a predetermined temperature (e.g., 100°C or higher, e.g., 120°C or higher), switching to an inert gas atmosphere, and heating the reaction system to a predetermined temperature (e.g., 100°C or higher). The heated reaction system may contain a zinc precursor and, optionally, a magnesium precursor. While raising the temperature of the reaction system to the shell forming temperature, the core particles and the chalcogen element precursor, and, optionally, the magnesium precursor, are added to the reaction system to form a shell of a desired composition. The zinc precursor and the chalcogen element precursor may be added simultaneously or sequentially during the reaction time, taking into account the desired shell composition. The method of adding the shell may be selected to form a shell of a desired composition (e.g., a single composition or a gradient / multilayer composition).

[0154] The shell formation temperature may be 200°C or higher, for example, 210°C or higher, 220°C or higher, 230°C or higher, 240°C or higher, 250°C or higher, 260°C or higher, 270°C or higher, 280°C or higher, 290°C or higher, 300°C or higher, or 310°C or higher. The shell formation temperature may be appropriately controlled within the range of 350°C or lower, 340°C or lower, 325°C or lower, or 310°C or lower. The shell formation temperature may be controlled in steps considering the shell composition and the precursor. In one embodiment, the first layer shell formation temperature may be higher or lower than the second layer shell formation temperature. The shell formation reaction time may be selected considering the desired shell composition, type of precursor, shell formation temperature, and desired shell thickness.

[0155] The magnesium precursor may be supplied to the reaction system in the core formation step, the shell formation step, or both. In one embodiment, the magnesium precursor may be provided together with a zinc precursor (e.g., in the shell formation step). The magnesium precursor may include magnesium acetate, magnesium acetylacetonate, and magnesium alkylate (e.g., C1 to C10, C2-C4 dialkyl magnesium).

[0156] In one embodiment, the formation of the semiconductor nanocrystal shell may include reacting a zinc precursor with a selenium precursor, a sulfur precursor, or a combination thereof, and optionally with a magnesium precursor. In one embodiment, the formation of the semiconductor nanocrystal shell may include forming a first shell layer by reacting a zinc precursor and a selenium precursor in the presence of an optional magnesium precursor, and then forming a second shell layer by reacting a zinc precursor and a sulfur precursor in the presence of an optional magnesium precursor. In one embodiment, the step of forming the semiconductor nanocrystal shell may include reacting the zinc precursor with the selenium precursor and the sulfur precursor, and optionally with a magnesium precursor, to form a zinc, selenium, and sulfur-containing shell containing magnesium optionally.

[0157] In the method described above, the zinc precursor may include metal powder, metal oxide, alkylated metal compound, metal alkoxide (e.g., metal ethoxide), metal carboxylate (e.g., metal acetate), metal nitrate, metal percolate, metal sulfate, metal acetylacetonate, metal halide, metal cyanide, metal hydroxide, or a combination thereof. Examples of zinc precursors may include, but are not limited to, dimethyl zinc, diethyl zinc, zinc acetate, zinc acetylacetonate, zinc iodide, zinc bromide, zinc chloride, zinc fluoride, zinc carbonate, zinc cyanide, zinc nitrate, zinc oxide, zinc peroxide, zinc perchlorate, zinc sulfate, and combinations thereof.

[0158] The above selenium precursor may include, but is not limited to, selen-trioctylphosphine (Se-TOP), selen-tributylphosphine (Se-TBP), selen-triphenylphosphine (Se-TPP), selen-diphenylphosphine (Se-DPP), or a combination thereof.

[0159] The above tellurium precursor may include, but is not limited to, Te-TOP (tellurtrioctylphosphine), tellur-tributylphosphine (Te-TBP), tellur-triphenylphosphine (Te-TPP), tellur-diphenylphosphine (Te-DPP), or a combination thereof.

[0160] The above sulfur precursor may include hexanethiol, octanethiol, decanthiol, dodecanethiol, hexadecanethiol, mercaptopropyl silane, sulfur-trioctylphosphine (S-TOP), sulfur-tributylphosphine (S-TBP), sulfur-triphenylphosphine (S-TPP), sulfur-trioctylamine (S-TOA), sulfur-octadecene (S-ODE), bistrimethylsilylsulfide, bistrimethylsilylmethyl sulfide, ammonium sulfide, sodium sulfide, or a combination thereof.

[0161] The above (first, second, and third) organic solvents may be the same or different. The above (first, second, and third) organic solvents (hereinafter referred to as organic solvents) are: a primary amine of C6 to C22 such as hexadecylamine; a secondary amine of C6 to C22 such as dioctylamine; a tertiary amine of C6 to C40 such as trioctylamine; a nitrogen-containing heterocyclic compound such as pyridine; an olefin of C6 to C40 such as octadecene; an aliphatic hydrocarbon of C6 to C40 such as hexadecane, octadecane, or squalane; an aromatic hydrocarbon substituted with a C6 to C30 alkyl group such as phenyldodecane, phenyltetradecane, or phenylhexadecane; a primary, secondary, or tertiary phosphine substituted with at least one (e.g., one, two, or three) C6 to C22 alkyl group (e.g., trioctylamine); (e.g., It may include phosphine oxides substituted with one, two, or three C6 to C22 alkyl groups (e.g., trioctylphosphine oxide), C12 to C22 aromatic ethers such as phenyl ether and benzyl ether, or combinations thereof.

[0162] The first organic ligand, the second organic ligand, and the third organic ligand may be the same. The first organic ligand, the second organic ligand, and the third organic ligand may be different. Specific details regarding the first organic ligand, the second organic ligand, and the third organic ligand are as described above regarding the organic ligand. In one embodiment, the second organic ligand may include a fatty acid (having an aliphatic hydrocarbon group of C5 or more, C10 or more, or C15 or more), and the third organic ligand may include an organic amine (e.g., a primary amine having one aliphatic hydrocarbon group or an aromatic hydrocarbon group having 5 or more, 10 or more, or 15 or more carbon atoms, e.g., RNH2, where R is an aliphatic hydrocarbon group (alkyl, alkenyl, or alkynyl), or an aryl group of C6 to C40) or a combination thereof. The number of carbon atoms in an aliphatic hydrocarbon group may be 5 or more, 10 or more, 15 or more, 16 or more, 17 or more, 18 or more, 19 or more, or 20 or more and 50 or less, 40 or less, or 30 or less.

[0163] When synthesizing the core, the content of the second organic ligand and the third organic ligand can be appropriately selected by taking into account the type of organic ligand, the type of precursor, etc. The content of the second organic ligand (or the third organic ligand) may be 0.1 mole or more, 0.2 mole or more, 0.3 mole or more, 0.4 mole or more, 0.5 mole or more, 0.6 mole or more, 0.7 mole or more, 0.8 mole or more, 0.9 mole or more, 1 mole or more, 2 mole or more, 3 mole or more, 4 mole or more, or 5 mole or more per mole of zinc precursor. The content of the second organic ligand (or third organic ligand) may be 20 moles or less, 19 moles or less, 18 moles or less, 17 moles or less, 16 moles or less, 15 moles or less, 14 moles or less, 13 moles or less, 12 moles or less, 10 moles or less, 9 moles or less, 8 moles or less, 7 moles or less, 6 moles or less, 5 moles or less, 4 moles or less, 3 moles or less, 2 moles or less, or 1 mole or less per mole of zinc precursor.

[0164] The molar ratio between the second organic ligand and the third organic ligand (second organic ligand: third organic ligand) may be 1:0.1 or greater, e.g. 1:0.5 or greater, 1:0.9 or greater, or 1:1 or greater, and 1:10 or less, e.g. 1:5 or less, 1:2.5 or less, or 1:1.5 or less.

[0165] The amount of magnesium precursor used in a core or shell formation reaction can be appropriately controlled by taking into account the type of precursor, reaction solvent, etc.

[0166] In one embodiment, the selenium precursor, the tellurium precursor, and the metal hydride compound may be injected into the zinc precursor organic solution in a mixed state with an organic ligand, optionally. In another embodiment, the selenium precursor, the tellurium precursor, and the metal hydride compound may be injected sequentially into the zinc precursor organic solution.

[0167] The content and concentration of each precursor within the core formation reaction system and the shell formation reaction system can be selected considering the desired core and shell compositions and the reactivity between the precursors. For example, the ratio between each precursor can be adjusted considering the desired composition (Zn, S, Se) of the final quantum dot. The composition of the final quantum dot can be confirmed by appropriate analytical means, such as inductively coupled plasma atomic emission analysis.

[0168] After the core and / or shell formation step, By adding a nonsolvent to the reaction product, the nanocrystalline particles (e.g., quantum dots or cores) coordinated with the ligand compound can be separated. The nonsolvent may be a polar solvent that is miscible with the solvent used in the core formation and / or shell formation reaction but cannot disperse the prepared nanocrystalline particles. The nonsolvent may be determined based on the solvent used in the reaction and may include, for example, acetone, ethanol, butanol, isopropanol, ethanediol, water, tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), diethyl ether, formaldehyde, acetaldehyde, ethylene glycol, solvents having solubility parameters similar to those listed above, or combinations thereof. Separation may be achieved using centrifugation, precipitation, chromatography, or distillation. The separated nanocrystalline particles may be washed by adding a washing solvent as necessary. The cleaning solvent is not particularly limited and may use a solvent having a solubility parameter similar to that of the ligand, such as hexane, heptane, octane, chloroform, toluene, benzene, etc.

[0169] The above organic ligand may not include a polyfunctional organic compound comprising a thiol residue; and at least one of an amino group and a carboxylic acid group. The above organic ligand may not include glutathione.

[0170] The above (cadmium-free) quantum dots may be water-insoluble. When dispersed in water, the above quantum dots may exhibit an average particle size of 300 nm or more, 400 nm or more, 500 nm or more, or 900 nm or more in dynamic light scattering analysis. The above quantum dots may be dispersed in an organic solvent (e.g., toluene, octane, etc.) to form a quantum dot organic solution having an average particle size of 500 nm or less, 400 nm or less, 300 nm or less, 200 nm or less, 100 nm or less, 90 nm or less, 50 nm or less, e.g., 30 nm or less, or 20 nm or less in dynamic light scattering analysis.

[0171] A composition of one embodiment may comprise the aforementioned quantum dot(s) (e.g., a plurality of); optionally a monomer, a dispersant, or a combination thereof; and a (organic) solvent (and / or liquid vehicle). The dispersant may disperse the quantum dots. The dispersant may comprise a compound containing a carboxylic acid group (monomer or polymer). The composition may further comprise a (photo)polymerizable monomer containing a carbon-carbon double bond, and optionally a (thermal or photo) initiator. The composition may be a photosensitive composition.

[0172] Detailed information regarding quantum dots within the above composition is as described above. The content of quantum dots within the composition can be appropriately adjusted in consideration of desired end uses (e.g., color filters, etc.). In one embodiment, the content of quantum dots may be 1 wt% or more based on the total weight or total solid content of the composition, e.g., 2 wt% or more, 3 wt% or more, 4 wt% or more, 5 wt% or more, 6 wt% or more, 7 wt% or more, 8 wt% or more, 9 wt% or more, 10 wt% or more, 15 wt% or more, 20 wt% or more, 25 wt% or more, 30 wt% or more, 35 wt% or more, or 40 wt% or more. The content of quantum dots may be 70 wt% or less based on the total weight or total solid content of the composition, e.g., 65 wt% or less, 60 wt% or less, 55 wt% or less, or 50 wt% or less. The content based on the total solid content in the composition may correspond to the content of the corresponding component in the composite to be described later.

[0173] In a composition according to one embodiment, the dispersant can contribute to ensuring the dispersibility of the quantum dots. In one embodiment, the dispersant may include an organic compound (e.g., a monomer or a polymer) (e.g., containing a carboxylic acid group). The binder polymer may be an insulating polymer.

[0174] The above-mentioned carboxylic acid group-containing organic compound is a monomer combination or copolymer thereof comprising a first monomer having a carboxylic acid group and a carbon-carbon double bond, a second monomer having a carbon-carbon double bond and a hydrophobic residue and not containing a carboxylic acid group, and optionally a third monomer having a carbon-carbon double bond and a hydrophilic residue and not containing a carboxylic acid group;

[0175] A multiple aromatic ring containing a carboxylic acid group (-COOH) having a skeletal structure in which two aromatic rings within the main chain are bonded to a quaternary carbon atom that is a constituent atom of another cyclic residue (hereinafter, cardo binder); or

[0176] A combination of these may be included. The dispersant may include the aforementioned first monomer, second monomer, and optionally the third monomer.

[0177] In the above composition, the content of the dispersant (or binder polymer) may be 0.5 wt% or more, for example, 1 wt% or more, 5 wt% or more, 10 wt% or more, 15 wt% or more, or 20 wt% or more, based on the total weight of the composition, but is not limited thereto. The content of the dispersant (or binder polymer) may be 35 wt% or less, for example, 33 wt% or less, or 30 wt% or less, based on the total weight of the composition. The content of the dispersant (or binder polymer) may be 0.5 wt% to 55 wt% based on the total weight of the solid content of the composition.

[0178] The above composition may include a polymerizable (e.g., photopolymerizable) monomer comprising the carbon-carbon double bond. The monomer may include a (e.g., photopolymerizable) (meth)acrylic monomer. The monomer may be a precursor for an insulating polymer.

[0179] The content of the monomer may be 0.5% by weight or more, for example, 1% by weight or more or 2% by weight or more, based on the total weight or total solid content of the composition. The content of the photopolymerizable monomer may be 30% by weight or less, for example, 28% by weight or less, 25% by weight or less, 23% by weight or less, 20% by weight or less, 18% by weight or less, 17% by weight or less, 16% by weight or less, or 15% by weight or less, based on the total weight or total solid content of the composition.

[0180] The (photo)initiator included in the above composition is intended for the (photo)polymerization of the aforementioned monomer. The initiator is a compound capable of promoting a radical reaction (e.g., radical polymerization of the monomer) by generating radical chemical species under mild conditions (e.g., by heat or light). The initiator may be a thermal initiator or a photoinitiator. The initiator is not particularly limited and can be appropriately selected.

[0181] In the above composition, the content of the initiator can be appropriately adjusted by taking into account the type and content of the polymerizable monomer used. In one embodiment, the content of the initiator may be 0.01 wt% or more, e.g., 1 wt% or more, and 10 wt% or less, e.g., 9 wt% or less, 8 wt% or less, 7 wt% or less, 6 wt% or less, or 5 wt% or less, based on the total weight of the composition (or total weight of the solid content), but is not limited thereto.

[0182] The above composition may further include a (multifunctional or monofunctional) thiol compound having at least one thiol group at the terminal end, metal oxide microparticles, or a combination thereof.

[0183] The metal oxide microparticles may include TiO2, SiO2, BaTiO3, Ba2TiO4, ZnO, or a combination thereof. The content of the metal oxide in the composition may be 1 wt% or more, 5 wt% or more, or 10 wt% or more and 50 wt% or less, 40 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, 10 wt% or less, or 5 wt% or less, based on the total weight of the composition (or its solid content weight). The metal oxide microparticles may be non-luminescent.

[0184] The diameter of the metal oxide microparticles is not particularly limited and can be appropriately selected. The diameter of the metal oxide microparticles may be 100 nm or more, e.g. 150 nm or more, 200 nm or more, and 1000 nm or less, or 800 nm or less. Here, the term metal oxide may include oxides of metals or metalloids.

[0185] The above (multi) thiol compound may be a dithiol compound, a trithiol compound, a tetrathiol compound, or a combination thereof. For example, the above thiol compound may be glycol di-3-mercaptopropionate, glycol dimercaptoacetate, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptopropionate), pentaerythritol tetrakis(2-mercaptoacetate), 1,6-hexanedithol, 1,3-propanedithiol, 1,2-ethanedithiol, polyethylene glycol dithiol containing 1 to 10 repeating units of ethylene glycol, or a combination thereof.

[0186] The content of the above (multiple) thiol compound may be 50 wt% or less, 40 wt% or less, 30 wt% or less, 20 wt% or less, 10 wt% or less, 9 wt% or less, 8 wt% or less, 7 wt% or less, 6 wt% or less, or 5 wt% or less, based on the total weight of the composition (or the total weight of the solids). The content of the above thiol compound may be 0.1 wt% or more, for example, 0.5 wt% or more, 1 wt% or more, 5 wt% or more, 10 wt% or more, or 15 wt% or more, based on the total weight of the composition (or the total weight of the solids).

[0187] The above composition may further comprise an organic solvent (or liquid vehicle, hereinafter referred to as solvent). The types of solvents that can be used are not particularly limited. Non-limiting examples of the solvent or liquid vehicle include ethyl 3-ethoxypropionate; ethylene glycols such as ethylene glycol, diethylene glycol, polyethylene glycol, etc.; glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, diethylene glycol monomethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, etc.; glycol ether acetates such as ethylene glycol acetate, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, etc.; and propylene glycols such as propylene glycol. Propylene glycol ethers such as propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, propylene glycol dimethyl ether, dipropylene glycol dimethyl ether, propylene glycol diethyl ether, and dipropylene glycol diethyl ether; propylene glycol ether acetates such as propylene glycol monomethyl ether acetate and dipropylene glycol monoethyl ether acetate; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; dimethyl sulfoxides; ketones such as methyl ethyl ketone (MEK), methyl isobutyl ketone (MIBK), and cyclohexanone; petroleum products such as solvent naphtha; esters such as ethyl acetate, butyl acetate, and ethyl sulfate; Ethers such as tetrahydrofuran, diethyl ether, dipropyl ether, and dibutyl ether, chloroform, C1 to C40 aliphatic hydrocarbons (e.g., alkanes, alkenes, or alkynes), C1 to C40 aliphatic hydrocarbons substituted with a halogen (e.g., chlorine) (e.g., dichloroethane, trichloromethane, etc.), C6 to C40 aromatic hydrocarbons (e.g., toluene, xylene, etc.), C6 to C40 aromatic hydrocarbons substituted with a halogen (e.g., chlorine) or combinations thereof are included but not limited thereto.

[0188] The type and amount of the above organic solvent are appropriately determined by considering the types and amounts of the aforementioned major components (i.e., quantum dots, dispersants, polymerizable monomers, initiators, and thiol compounds if present) and other additives described below. The above composition contains the solvent in an amount remaining after deducting the desired solid content (non-volatile component).

[0189] The above composition (e.g., an inkjet composition) may have a viscosity of 4 cPs or more, 5 cPs or more, 5.5 cPs or more, 6.0 cPs or more, or 7.0 cPs or more at 25°C. The above composition may have a viscosity of 12 cPs or less, 10 cPs or less, or 9 cPs or less at 25°C.

[0190] When used in an inkjet, the above composition is extruded onto a substrate at room temperature and, for example, can form a quantum dot-polymer composite film or a pattern thereof by heating. The ink composition may have the aforementioned viscosity and a surface tension of 21 mN / m or more, 22 mN / m or more, 23 mN / m or more, 24 mN / m or more, 25 mN / m or more, 26 mN / m or more, 27 mN / m or more, 28 mN / m or more, 29 mN / m or more, 30 mN / m or more, or 31 mN / m or more and 40 mN / m or less, 39 mN / m or less, 38 mN / m or less, 36 mN / m or less, 35 mN / m or less, 34 mN / m or less, 33 mN / m or less, or 32 mN / m or less. The above ink composition may have a surface tension of 31 mN / m or less, 30 mN / m or less, 29 mN / m or less, or 28 mN / m or less.

[0191] The composition of one embodiment may further include, for example, an additive included in a photoresist composition or an ink composition. The additive may include a light diffusing agent, a leveling agent, a coupling agent, etc. For specific details, reference may be made to the contents described in, for example, US-2017-0052444-A1.

[0192] The composition according to one embodiment may be prepared by a method comprising the steps of: preparing a quantum dot dispersion comprising the aforementioned quantum dots, the aforementioned dispersant, and a solvent; and mixing the initiator; a polymerizable monomer (e.g., an acrylic monomer); optionally a thiol compound; optionally metal oxide microparticles; and optionally the aforementioned additive into the quantum dot dispersion. Each of the aforementioned components may be mixed sequentially or simultaneously, and the order thereof is not particularly limited.

[0193] A composition according to one embodiment can be used to provide a pattern of a quantum dot complex (e.g., a quantum dot polymer complex). The composition can provide a quantum dot-polymer complex by (e.g., radical) polymerization. A composition according to one embodiment may be a quantum dot-containing photoresist composition applicable to photolithography. A composition according to one embodiment may be an ink composition capable of providing a pattern by a printing method (e.g., a droplet extrusion method such as inkjet printing).

[0194] The quantum dot complex (polymer complex) comprises a (polymer) matrix; and the aforementioned quantum dot(s) dispersed within the matrix. The quantum dot complex may further comprise metal oxide microparticles dispersed within the matrix. The (polymer) matrix may comprise a cross-linked polymer, a linear polymer, or a combination thereof. The cross-linked polymer may comprise a thiolene resin, a cross-linked poly(meth)acrylate, a cross-linked polyurethane, a cross-linked epoxy resin, a cross-linked vinyl polymer, a cross-linked silicone resin, or a combination thereof. The linear polymer may comprise a carboxylic acid-containing repeating unit.

[0195] The above matrix may comprise the aforementioned dispersant (e.g., a binder monomer or polymer containing a carboxylic acid group), a polymerization product of a polymerizable monomer comprising one or more carbon-carbon double bonds (e.g., two or more, three or more, four or more, or five or more) (e.g., an insulating polymer), and optionally a polymerization product between the polymerizable monomer and a thiol compound having at least one (e.g., two or more) thiol group at the terminal end.

[0196] In one embodiment, the polymer matrix may comprise a cross-linked polymer, a linear polymer, or a combination thereof. The cross-linked polymer may comprise a thiolene resin, a cross-linked poly(meth)acrylate, or a combination thereof. In one embodiment, the cross-linked polymer may be a polymerization product of the aforementioned polymerizable monomer and, optionally, a multi-thiol compound. Descriptions of the quantum dots, dispersants, polymerizable monomers, and multi-thiol compounds are as described above.

[0197] A film of a quantum dot composite (e.g., which can be patterned) may have a thickness of 30 μm (micrometer) or less, e.g., 25 μm (micrometer) or less, 20 μm or less, 15 μm or less, 10 μm or less, 8 μm or less, or 7 μm or less, and a thickness greater than 2 μm, e.g., 3 μm or more, 3.5 μm or more, 4 μm or more, 5 μm or more, or 6 μm or more.

[0198] In another embodiment, the patterned film of the quantum dot complex may include one or more repeating sections configured to emit a predetermined light. In one embodiment, the repeating section may include a first section configured to emit a first light. The repeating section may include a second section that emits a second light having a maximum peak wavelength different from that of the first light. At least one of the first section and the second section may include the aforementioned quantum dot complex. The first light or the second light may be red light having a maximum emission peak wavelength of 600 nm to 650 nm (e.g., 620 nm to 650 nm) or green light having a maximum emission peak wavelength of 500 nm to 550 nm (e.g., 510 nm to 540 nm). The patterned film may further include a third section that emits or passes a third light (e.g., blue light) different from the first light and the second light. The third light may include excitation light. The third light may include blue light with a maximum peak wavelength in the range of 380 nm or more and 480 nm or less.

[0199] A patterned quantum dot composite film can be manufactured using a photoresist composition. This method comprises the steps of: forming a film of the aforementioned composition on a substrate (S1); prebaking the film according to selection (S2); exposing a selected area of ​​the film to light (e.g., wavelength 400 nm or less) (S3); and developing the exposed film with an alkaline developer to obtain a pattern of the quantum dot polymer composite (S4).

[0200] Referring to FIG. 2a, the aforementioned composition is applied to a substrate to a predetermined thickness using a suitable method such as spin coating or slit coating to form a film. The formed film may undergo pre-baking (PRB) depending on the choice. Conditions such as temperature, time, and atmosphere for pre-baking are known and can be appropriately selected.

[0201] The formed (or optionally pre-baked) film is exposed to light of a predetermined wavelength under a mask having a predetermined pattern. The wavelength and intensity of the light can be selected by considering the type and content of the photoinitiator, the type and content of the quantum dots, etc.

[0202] When the exposed film is treated with an alkaline developer (e.g., immersion or spraying), the unexposed portion of the film is dissolved and a desired pattern is obtained. If necessary, the obtained pattern may be post-baked (POB) at a temperature of, for example, 150°C to 230°C for a predetermined time (e.g., 10 minutes or more, or 20 minutes or more) to improve the crack resistance and solvent resistance of the pattern.

[0203] When a quantum dot composite pattern has multiple repeating sections, a plurality of compositions are prepared for the formation of each repeating section, comprising quantum dots having desired luminescent properties (photoluminescent peak wavelength, etc.) (e.g., red-emitting quantum dots, green quantum dots, or optionally blue quantum dots), and the aforementioned pattern formation process is repeated for each composition a required number of times (e.g., two or more times, or three or more times) to obtain a quantum dot-polymer composite of a desired pattern. For example, the quantum dot-polymer composite may be a pattern in which two or more different color sections (e.g., RGB color sections) are repeated. Such a quantum dot-polymer composite pattern can be advantageously used as a photoluminescent color filter in a display device.

[0204] A quantum dot composite pattern can be manufactured using an ink composition configured to form a pattern by an inkjet method. Referring to FIG. 2b, this method may include the steps of: manufacturing an ink composition; providing a substrate (e.g., having pixel regions patterned by electrodes and optionally banks, etc.); depositing the ink composition on the substrate (or pixel regions) to form, for example, a first quantum dot layer (or a first repeating section); and depositing the ink composition on the substrate (or pixel regions) to form, for example, a second quantum dot layer (or a second repeating section). The formation of the first quantum dot layer and the formation of the second quantum dot layer may be performed simultaneously or sequentially.

[0205] Deposition of the ink composition can be achieved using a suitable liquid crystal ejection device, such as an inkjet or nozzle printing system having an ink reservoir and one or more print heads. The deposited ink composition can be subjected to the removal of the solvent and polymerization by heating to provide a (first or second) quantum dot layer. This method can form a highly precise quantum dot-polymer composite film or pattern in a short time in a simple manner.

[0206] The aforementioned quantum dots or quantum dot complexes (patterns) may be included in electronic devices. Such electronic devices may include, but are not limited to, display elements, light-emitting diodes (LEDs), organic light-emitting diodes (OLEDs), quantum dot LEDs, sensors, solar cells, imaging sensors, photodetectors, or liquid crystal display elements. The aforementioned quantum dots may be included in electronic apparatus. Such electronic apparatus may include, but is not limited to, portable terminal devices, monitors, notebook PCs, televisions, electronic display boards, cameras, automobiles, etc. The electronic apparatus may be a portable terminal device, monitor, notebook PC, or television that includes a display element (or light-emitting element) containing quantum dots. The electronic apparatus may be a camera or portable terminal device that includes an image sensor containing quantum dots. The electronic apparatus may be a camera or automobile that includes a photodetector containing quantum dots.

[0207] The above device (display device or light-emitting device) may further include a light-emitting element and, optionally, a light source. The light-emitting element may include a light-emitting layer. The light-emitting element may further include a substrate, and the light-emitting layer may be disposed on one surface of the substrate. The light-emitting layer may include a film of a quantum dot complex or a patterned film. The light source may be configured to provide incident light to the light-emitting element. The incident light may have a photoluminescence peak wavelength in the range of 440 nm or more, e.g., 450 nm or more, and 500 nm or less, e.g., 480 nm or less, 470 nm or less, or 460 nm or less.

[0208] In one embodiment, the light-emitting element or the light-emitting layer may include a sheet of the quantum dot composite. Referring to FIG. 3, the photoluminescent type device includes a backlight unit (410) and a liquid crystal panel (420), and the backlight unit (410) may include a quantum dot polymer composite sheet (QD sheet). Specifically, the backlight unit (410) may have a structure in which a reflector, a light guide plate (LGP), a light source (blue LED, etc.), a quantum dot polymer composite sheet (QD sheet), and an optical film (prism, double brightness enhance film (DBEF), etc.) are laminated. The liquid crystal panel (420) is placed on top of the backlight unit (410) and may have a structure including a liquid crystal and a color filter between two polarizers (Pol). The quantum dot polymer composite sheet (QD sheet) may include quantum dots that emit red light and quantum dots that emit green light by absorbing light from a light source. Blue light provided from a light source can be converted into white light by combining with red and green light emitted from quantum dots as it passes through a quantum dot polymer composite sheet. This white light can be separated into blue, green, and red light by color filters within the liquid crystal panel and emitted externally pixel by pixel.

[0209] When the light-emitting layer comprises a patterned film of a quantum dot complex, the patterned film comprises repeating sections configured to emit desired light. The repeating sections may include a first section. The first section may be a red light emitting section. The repeating sections may include a second section. The second section may be a green light emitting section. The repeating sections may include a third section. The third section may be a section that emits or transmits blue light. Details regarding the first, second, and third sections are as described above.

[0210] The light source may be an element that emits excitation light. The excitation light may include blue light and, optionally, green light. The light source may include an LED. The light source may include an organic LED (OLED). On the front surface (light-emitting surface) of the first compartment and the second compartment, an optical element that blocks (e.g., reflects or absorbs) blue light (and, optionally, green light), such as a blue light (and, optionally, green light) blocking layer or a first optical filter as described below, may be disposed. If the light source includes a blue light-emitting organic light-emitting diode and a green light-emitting organic light-emitting diode, a green light removal filter may be further disposed on the third compartment through which the blue light passes.

[0211] The light source comprises a plurality of light-emitting units corresponding to the first section and the second section, respectively, and the light-emitting unit may include a first electrode and a second electrode facing each other, and a (organic) electroluminescent layer disposed between the first electrode and the second electrode. The electroluminescent layer may include an organic light-emitting material. For example, each light-emitting unit of the light source may include an electroluminescent element (e.g., an organic light-emitting diode) configured to emit light of a predetermined wavelength (e.g., blue light, green light, or a combination thereof). The structure and material of the electroluminescent element and the organic light-emitting diode are known and are not particularly limited.

[0212] FIGS. 4a and 4b show a schematic cross-sectional view of a display element according to one embodiment. Referring to FIGS. 4a and 4b, the light source includes an organic light-emitting diode that emits blue light (and optionally green light). The organic light-emitting diode may include two or more pixel electrodes formed on a substrate, a pixel defining film formed between adjacent pixel electrodes, an organic light-emitting layer formed on each pixel electrode, and a common electrode layer formed on the organic light-emitting layer. A thin-film transistor and a substrate may be disposed below the organic light-emitting diode. The pixel regions of the OLED may be disposed corresponding to the first, second, and third sections described below.

[0213] A stacked structure comprising a pattern of a quantum dot complex (e.g., a first section containing red quantum dots and a second section containing green quantum dots) and a substrate may be disposed on the light source. Blue light emitted from the light source is incident on the first section and the second section, emitting red and green light, respectively. Blue light emitted from the light source may pass through the third section. An element that blocks excitation light (a first optical filter or an excitation light blocking layer) may be disposed between the quantum dot complex layer (R, G) and the substrate, depending on the choice. If the excitation light includes blue light and green light, a green light blocking filter may be added to the third section. The first optical filter or the excitation light blocking layer will be described in more detail below.

[0214] Such a device can be manufactured by separately manufacturing the aforementioned stacked structure and an LED or OLED (e.g., blue light emitting) and then combining them. Alternatively, the device may be manufactured by directly forming a pattern of a quantum dot complex on the LED or OLED.

[0215] The substrate may be a substrate comprising an insulating material. The substrate may include, but is not limited to, glass; various polymers such as polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyester, polycarbonate, polyacrylate, etc.; polysiloxane (e.g., PDMS); inorganic materials such as Al2O3, ZnO, etc.; or a combination thereof. The thickness of the substrate may be appropriately selected considering the substrate material, etc., and is not particularly limited. The substrate may be flexible. The substrate may be configured to have a transmittance of 50% or more, 60% or more, 70% or more, 80% or more, or 90% or more for light emitted from the quantum dots.

[0216] A wiring layer including thin-film transistors, etc. is formed on the substrate. The wiring layer may further include a gate line, a holding voltage line, a gate insulating film, a data line, a source electrode, a drain electrode, a semiconductor, a protective film, etc. The detailed structure of the wiring layer may vary depending on the embodiment. The gate line and the holding voltage line are electrically isolated from each other, and the data line crosses the gate line and the holding voltage line insulatedly. The gate electrode, the source electrode, and the drain electrode each constitute the control terminal, input terminal, and output terminal of the thin-film transistor. The drain electrode is electrically connected to the pixel electrode described later.

[0217] The pixel electrode can function as an electrode (e.g., an anode) of a display device. The pixel electrode can be formed from a transparent conductive material such as indium tin oxide (ITO) or indium zinc oxide (IZO). The pixel electrode may also be formed from a light-blocking material such as gold (Au), platinum (Pt), nickel (Ni), tungsten (W), chromium (Cr), molybdenum (Mo), iron (Fe), cobalt (Co), copper (Cu), palladium (Pd), or titanium (Ti). The pixel electrode may have a two-layer structure in which the aforementioned transparent conductive material and the aforementioned light-blocking material are sequentially stacked.

[0218] Between two adjacent pixel electrodes, a pixel define layer (PDL) may be formed that overlaps with the ends of the pixel electrodes and separates the pixel electrodes into pixel units. The pixel define layer may serve as an insulating layer and electrically block the two or more pixel electrodes.

[0219] The pixel defining layer covers only a portion of the upper surface of the pixel electrode, and the remaining portion of the pixel electrode not covered by the pixel defining layer may form an opening. An organic light-emitting layer, to be described later, may be formed on the area defined by the opening.

[0220] The organic light-emitting layer is defined as a pixel region by the aforementioned pixel electrode and pixel defining layer. That is, a region in which an organic light-emitting unit layer is formed in contact with a pixel electrode separated by the pixel defining layer can be defined as a pixel region. In a display device according to one embodiment, the organic light-emitting layer may be defined as a first pixel region, a second pixel region, and a third pixel region, and each pixel region is spaced apart by a predetermined interval by the pixel defining layer.

[0221] The organic light-emitting layer may emit a third light that belongs to the visible light region or the UV region. Each of the first to third pixel regions of the organic light-emitting layer may emit the third light. In one embodiment, the third light may include light having high energy among the light in the visible light region, for example, blue light (and optionally green light). If each pixel region of the organic light-emitting layer is designed to emit the same light, each pixel region of the organic light-emitting layer may be formed of the same or similar material or exhibit the same or similar physical properties. Therefore, the difficulty of the organic light-emitting layer formation process can be significantly reduced, and such a display device can be easily applied to large-scale / large-area processes. However, the organic light-emitting layer according to one embodiment is not necessarily limited thereto, and the organic light-emitting layer may be configured to emit two or more different lights.

[0222] The organic light-emitting layer includes an organic light-emitting unit layer for each pixel area, and each organic light-emitting unit layer may further include auxiliary layers (e.g., a hole injection layer, a hole transport layer, an electron transport layer, etc.) in addition to the light-emitting layer.

[0223] The common electrode can function as the cathode of a display device. The common electrode can be formed from a transparent conductive material such as indium tin oxide (ITO) or indium zinc oxide (IZO). The common electrode can be formed integrally on the organic light-emitting layer.

[0224] A flattening layer or a passivation layer (not shown) may be formed on the common electrode. The flattening layer may include an insulating material (e.g., transparent) to ensure electrical insulation from the common electrode.

[0225] In one embodiment, the display device further comprises a lower substrate, a polarizing plate disposed below the lower substrate, and a liquid crystal layer interposed between the stacked structure and the lower substrate, wherein the stacked structure may be arranged such that the photoluminescent layer faces the liquid crystal layer. The display device may further comprise a polarizing plate between the liquid crystal layer and the light-emitting layer. The light source may further comprise an LED and, optionally, a light guide plate.

[0226] A display device (e.g., a liquid crystal display device) according to a non-limiting embodiment is described with reference to the drawings. FIG. 5 shows a schematic cross-sectional view of a liquid crystal display element according to a non-limiting embodiment. Referring to FIG. 3, a display element of one embodiment includes a liquid crystal panel (200), a polarizing plate (300) disposed below the liquid crystal panel (200), and a backlight unit (BLU) disposed below the polarizing plate (300).

[0227] The liquid crystal panel (200) comprises a lower substrate (210), a stacked structure, and a liquid crystal layer (220) interposed between the stacked structure and the lower substrate. The stacked structure comprises a transparent substrate (240) and a self-emissive layer (230) comprising a pattern of a quantum dot polymer composite.

[0228] The lower substrate (210), also referred to as an array substrate, may be a transparent insulating material substrate. The details regarding the substrate are as described above. A wiring board (211) is provided on the upper surface of the lower substrate (210). The wiring board (211) may include, but is not limited to, a plurality of gate wires (not shown) defining pixel regions, data wires (not shown), thin-film transistors provided adjacent to the intersection of the gate wires and data wires, and pixel electrodes for each pixel region. The specific details of such a wiring board are known and are not particularly limited.

[0229] A liquid crystal layer (220) is provided on the above wiring board (211). The liquid crystal layer (220) may include alignment layers (221) above and below the layer for the initial alignment of the liquid crystal material contained therein. Specific details regarding the liquid crystal material and alignment layers (e.g., liquid crystal material, alignment layer material, method of forming the liquid crystal layer, thickness of the liquid crystal layer, etc.) are known and are not particularly limited.

[0230] A lower polarizer (300) is provided below the lower substrate. The material and structure of the polarizer (300) are known and are not particularly limited. A backlight unit (e.g., emitting blue light) is provided below the polarizer (300). An upper optical element or polarizer (300) may be provided between the liquid crystal layer (220) and the transparent substrate (240), but is not limited thereto. For example, the upper polarizer may be placed between the liquid crystal layer (220) and the photoluminescent layer (230). The polarizer may be any polarizer that can be used in a liquid crystal display element. The polarizer may be triacetyl cellulose (TAC) having a thin thickness of 200 μm or less, but is not limited thereto. In another embodiment, the upper optical element may be a refractive index controlling coating without a polarization function.

[0231] The backlight unit includes a light source (110). The light source may emit blue light or white light. The light source may include, but is not limited to, a blue LED, a white LED, a white OLED, or a combination thereof.

[0232] The backlight unit may further include a light guide plate (120). In one embodiment, the backlight unit may be edge-type. For example, the backlight unit may include a reflector (not shown), a light guide plate (not shown) provided on the reflector and for supplying a surface light source to a liquid crystal panel (200), and / or one or more optical sheets (not shown) located on the upper portion of the light guide plate, such as a diffuser plate, a prism sheet, etc., but is not limited thereto. The backlight unit may not include a light guide plate. In one embodiment, the backlight unit may be direct lighting type. For example, the backlight unit may have a reflector (not shown) and a plurality of fluorescent lamps arranged at regular intervals on the upper portion of the reflector, or may have a driving substrate for LEDs on which a plurality of light-emitting diodes are arranged, and may have a diffuser plate and, optionally, one or more optical sheets on the above. Details regarding such backlight units (e.g., details regarding each component such as light-emitting diodes, fluorescent lamps, light guide plates and various optical sheets, reflectors, etc.) are known and are not particularly limited.

[0233] On the bottom surface of the transparent substrate (240), a black matrix (241) is provided that includes an opening and covers gate lines, data lines, and thin-film transistors of a wiring board provided on the bottom substrate. For example, the black matrix (241) may have a grid shape. At the opening of the black matrix (241), a self-emissive layer (230) having a quantum dot-polymer composite pattern is provided, comprising a first section (R) that emits a first light (e.g., red light), a second section (G) that emits a second light (e.g., green light), and a third section (B) that emits / transmits, for example, blue light. If desired, the self-emissive layer may further include one or more fourth sections. The fourth section may include quantum dots that emit light of a different color (e.g., cyan, magenta, and yellow) than the light emitted from the first to third sections.

[0234] The sections forming a pattern in the above photoluminescent layer (230) can be repeated corresponding to pixel areas formed on the lower substrate. A transparent common electrode (231) may be provided on the above self-emissive color filter layer.

[0235] The third section (B) that transmits / emits blue light may be a transparent color filter that does not alter the emission spectrum of the light source. In this case, blue light emitted from the backlight unit may pass through a polarizer and a liquid crystal layer, be incident in a polarized state, and be emitted as is. If necessary, the third section may include a quantum dot that emits blue light.

[0236] As described above, if desired, the display device or light-emitting element of one embodiment may further have an excitation light blocking layer or a first optical filter layer (hereinafter referred to as the first optical filter layer). The first optical filter layer may be disposed between the bottom surface of the first section (R) and the second section (G) and a substrate (e.g., upper substrate 240) or on the upper surface of the substrate. The first optical filter layer may be a sheet having an opening in the portion corresponding to the pixel area (third section) that displays blue, and may be formed in the portion corresponding to the first and second sections. That is, as shown in FIGS. 4a, 4b, and 5, the first optical filter layer may be integrally formed in the remaining positions excluding the position overlapping with the third section, but is not limited thereto. Two or more first optical filter layers may be spaced apart from each other at positions overlapping with the first and second sections, and optionally with the third section. If the light source includes a green light emitting element, a green light blocking layer may be disposed on the third section.

[0237] The first optical filter layer may, for example, block light in some wavelength regions of the visible light region and transmit light in the remaining wavelength regions, and may, for example, block blue light (or green light) and transmit light excluding blue light (or green light). The first optical filter layer may, for example, transmit green light, red light, and / or yellow light which is a mixture of these colors. The first optical filter layer may transmit blue light and block green light, and may be placed on a blue light emitting pixel.

[0238] The first optical filter layer can substantially block excitation light and transmit light in a desired wavelength range. The transmittance of the first optical filter layer for light in a desired wavelength range can be about 70% or more, 80% or more, 90% or more, or even 100%.

[0239] A first optical filter layer that selectively transmits red light may be positioned at a location overlapping with a red light emission section, and a first optical filter layer that selectively transmits green light may be positioned at a location overlapping with a green light emission section. The first optical filter layer may include at least one of a first region that blocks (e.g., absorbs) blue light and red light and selectively transmits light within a predetermined range (e.g., about 500 nm or more, about 510 nm or more, or about 515 nm or more and about 550 nm or less, about 545 nm or less, about 540 nm or less, about 535 nm or less, about 530 nm or less, about 525 nm or less, or about 520 nm or less), and a second region that blocks (e.g., absorbs) blue light and green light and selectively transmits light within a predetermined range (e.g., about 600 nm or more, about 610 nm or more, or about 615 nm or more and about 650 nm or less, about 645 nm or less, about 640 nm or less, about 635 nm or less, about 630 nm or less, about 625 nm or less, or about 620 nm or less). There is. When the light source emits a mixture of blue and green light, the first optical filter may further include a third region that selectively transmits blue light and blocks green light.

[0240] The first region may be positioned at a location overlapping with the green light emission section. The second region may be positioned at a location overlapping with the red light emission section. The third region may be positioned at a location overlapping with the blue light emission region.

[0241] The first region, the second region, and optionally the third region may be optically isolated. This first optical filter layer can contribute to improving the color purity of the display element.

[0242] The display element may further include a second optical filter layer (e.g., a red / green light or yellow light recycling layer) disposed between the photoluminescent layer and the liquid crystal layer (e.g., between the photoluminescent layer and the upper polarizer), which transmits at least a portion of the third light (excitation light) and reflects at least a portion of the first light and / or second light. The first light may be red light, the second light may be green light, and the third light may be blue light. The second optical filter layer may transmit only the third light (B) in the blue light wavelength region having a wavelength region of 500 nm or less, and may cause light in the wavelength region exceeding 500 nm, i.e., green light (G), yellow light, red light (R), etc., to be reflected without passing through the second optical filter layer (140). The reflected green light and red light may pass through the first and second sections and be emitted outside the display device (10).

[0243] The second optical filter layer or the first optical filter layer may be formed as a single layer having a relatively flat surface.

[0244] The first optical filter layer may include a polymer thin film containing a dye and / or pigment that absorbs light of a wavelength to be blocked. The second optical filter layer and the first optical filter layer may include a single layer having a low refractive index, for example, a transparent thin film with a refractive index of 1.4 or less, 1.3 or less, or 1.2 or less. The second optical filter layer or the first optical filter layer having a low refractive index may be, for example, porous silicon oxide, a porous organic material, a porous organic / inorganic composite, or a combination thereof.

[0245] The first optical filter layer or the second optical filter layer may include a plurality of layers with different refractive indices. The two layers with different refractive indices may be formed by alternately stacking. For example, the first and second optical filter layers may be formed by alternately stacking a material having a high refractive index and a material having a low refractive index.

[0246] Referring to FIG. 6a, the electronic device (10) includes a first electrode (11) and a second electrode (15) facing each other, and an active layer (13) located between the first electrode (11) and the second electrode (15) and including the aforementioned quantum dots.

[0247] In one embodiment, the electronic device including quantum dots may be an electroluminescent device. The quantum dots of the active layer (13) may be a light-emitting layer capable of emitting light of a certain wavelength by the energy of the formed excitons, wherein electrons and holes injected from the first electrode (11) and the second electrode (15) recombine to form excitons. Additionally, the electronic device including quantum dots may be a photodetector or a solar cell. Specifically, the quantum dots of the active layer (13) may be a light-absorbing layer that absorbs external photons, separates them into electrons and holes, and provides electrons and holes to the first electrode (11) and the second electrode (15).

[0248] A hole assist layer (12) may be located between the first electrode (11) and the active layer (13), and an electron assist layer (14) may be located between the second electrode (15) and the active layer (13).

[0249] The electronic device (10) may further include a substrate (not shown). The substrate may be placed on the side of the first electrode (11) or on the side of the second electrode (15). The substrate may be a substrate containing an insulating material (e.g., an insulating transparent substrate). Additionally, the substrate may include various polymers such as glass, polyester (e.g., polyethylene terephthalate (PET), polyethylene naphthalate (PEN)), polycarbonate, polyacrylate, polyimide, polyamideimide, etc., inorganic materials such as polysiloxane (e.g., PDMS), Al2O3, ZnO, etc., or a combination thereof, or may be made of a silicon wafer, etc. The term "transparent" may mean that the transmittance through which light of a certain wavelength (e.g., light emitted from quantum dots) passes is 85% or more, 88% or more, 90% or more, 95% or more, 97% or more, or 99% or more. The thickness of the substrate can be appropriately selected considering the substrate material, etc., and is not particularly limited. The transparent substrate may be flexible.

[0250] One of the first electrode (11) and the second electrode (15) is an anode and the other is a cathode. For example, the first electrode (11) may be an anode and the second electrode (15) may be a cathode.

[0251] The first electrode (11) may be made of a conductor, for example, a metal, a conductive metal oxide, or a combination thereof. The first electrode (11) may be made of a metal such as nickel, platinum, vanadium, chromium, copper, zinc, gold, or an alloy thereof, a conductive metal oxide such as zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), or fluorine-doped tin oxide, or a combination of a metal and an oxide such as ZnO and Al or SnO2 and Sb, but is not limited thereto. The second electrode (15) may be made of a conductor, for example, a metal, a conductive metal oxide and / or a conductive polymer. The second electrode (15) may be a metal such as aluminum, magnesium, calcium, sodium, potassium, titanium, indium, yttrium, lithium, gadolinium, silver, gold, platinum, tin, lead, cesium, barium, etc., or an alloy thereof, or a multilayer structure material such as LiF / Al, lithium oxide (Li2O) / Al, Liq / Al, LiF / Ca, and BaF2 / Ca, but is not limited thereto. Conductive metal oxides are as described above.

[0252] The work functions of the first electrode (11) and the second electrode (15) are not particularly limited and can be appropriately selected. The work function of the first electrode (11) may be higher or lower than the work function of the second electrode (15).

[0253] At least one of the first electrode (11) and the second electrode (15) may be a light-transmitting electrode, and the light-transmitting electrode may be made of a conductive metal oxide such as zinc oxide, indium oxide, tin oxide, indium tin oxide (ITO), indium zinc oxide (IZO), or fluorine-doped tin oxide, or a thin single layer or multiple layers of metal film. If either of the first electrode (11) and the second electrode (15) is an opaque electrode, it may be made of an opaque conductor such as aluminum (Al), silver (Ag), or gold (Au).

[0254] The thickness of the first electrode (11) and / or the second electrode (15) is not particularly limited and can be appropriately selected considering the device efficiency. For example, the thickness of the electrode may be 5 nm or more, e.g., 50 nm or more, and 100 μm or less, e.g., 10 μm or less, 1 μm or less, 900 nm or less, 500 nm or less, or 100 nm or less.

[0255] The active layer (13) includes the quantum dots described above. The active layer (13) may include a monolayer or a plurality of monolayer quantum dot layers. The plurality of monolayer layers may be 2 layers or more, 3 layers or more, or 4 layers or more, and 20 layers or less, 10 layers or less, 9 layers or less, 8 layers or less, 7 layers or less, or 6 layers or less. The active layer (13) may have a thickness of 5 nm or more, e.g., 10 nm or more, 20 nm or more, or 30 nm or more, and 200 nm or less, e.g., 150 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, or 50 nm or less. The active layer (13) may have a thickness of about 10 nm to 150 nm, about 10 nm to 100 nm, or about 10 nm to 50 nm.

[0256] The electronic device (10) may further include a hole assist layer (12). The hole assist layer (12) is located between the first electrode (11) and the active layer (13). The hole assist layer (12) may include a hole injection layer, a hole transport layer, an electron blocking layer (EBL), or a combination thereof. The hole assist layer (12) may be a single-component layer or a multilayer structure in which adjacent layers include different components.

[0257] The HOMO energy level of the hole assist layer (12) may have a HOMO energy level that can be matched with the HOMO energy level of the active layer (13) to enhance the mobility of holes transferred from the hole assist layer (12) to the active layer (13). For example, the hole assist layer (12) may include a hole injection layer located close to the first electrode (11) and a hole transport layer located close to the active layer (13).

[0258] The material included in the hole assist layer (12) (e.g., hole transport layer or hole injection layer) is not particularly limited and, for example, poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (Poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine), TFB), polyarylamine, poly(N-vinylcarbazole), poly(3,4-ethylenedioxythiophene), PEDOT, poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), polyaniline, polypyrrole, Carbon-based materials such as N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), m-MTDATA (4,4',4"-Tris[phenyl(m-tolyl)amino]triphenylamine), 4,4',4"-tris(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-toylamino)phenylcyclohexane (TAPC), p-type metal oxides (e.g., NiO, WO3, MoO3, etc.), graphene oxide, and their It may include at least one selected from the combination, but is not limited thereto.

[0259] When an electron blocking layer (EBL) is used, the electron blocking layer (EBL) is poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TPB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD). It may include at least one selected from 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl, α-NPD), m-MTDATA, 4,4',4"-tris(N-carbazolyl)-triphenylamine (4,4',4"-tris(N-carbazolyl)-triphenylamine, TCTA) and combinations thereof, but is not limited thereto.

[0260] In the hole assist layer(s), the thickness of each layer can be appropriately selected. For example, the thickness of each layer may be 5 nm or more, 10 nm or more, 15 nm or more, or 20 nm or more, and 50 nm or less, e.g., 40 nm or less, 35 nm or less, or 30 nm or less, but is not limited thereto.

[0261] The electron auxiliary layer (14) is located between the active layer (13) and the second electrode (15). The electron auxiliary layer (14) may include, for example, an electron injection layer (EIL) that facilitates electron injection, an electron transport layer (ETL) that facilitates electron transport, a hole blocking layer (HBL) that blocks the movement of holes, or a combination thereof. For example, the electron injection layer may be placed between the electron transport layer and the cathode (15). For example, the hole blocking layer (HBL) may be placed between the active layer and the electron transport (injection) layer, but is not limited thereto. The thickness of each layer may be appropriately selected, for example, the thickness of each layer may be 1 nm or more and 500 nm or less, but is not limited thereto. The electron injection layer may be an organic layer formed by deposition, and the electron transport layer may include inorganic oxide nanoparticles.

[0262] The electron transport layer (ETL) may comprise, for example, 1,4,5,8-naphthalene-tetracarboxylic dianhydride (NTCDA), bathocuproine (BCP), tris[3-(3-pyridyl)-methyl]borane (3TPYMB), LiF, Alq3, Gaq3, Inq3, Znq2, Zn(BTZ)2, BeBq2, ET204 (8-(4-(4,6-di(naphthalen-2-yl)-1,3,5-triazin-2-yl)phenyl)quinolone), 8-hydroxyquinolinato lithium (Liq), n-type metal oxides (e.g., ZnO, HfO2, etc.) and at least one selected from combinations thereof, but is not limited thereto.

[0263] Additionally, the electron transport layer (ETL) may include a plurality of nanoparticles. The nanoparticles may include metal oxides containing zinc, for example, zinc oxide, zinc magnesium oxide, or a combination thereof. The metal oxide is Zn 1-x Mx It may include O (wherein M is Mg, Ca, Zr, W, Li, Ti, Y, Al, or a combination thereof, and 0 ≤ x ≤ 0.5). In this formula, x may be 0.01 or more and 0.3 or less, e.g., 0.25 or less, 0.2 or less, or 0.15 or less. The absolute value of the LUMO of the aforementioned quantum dots included in the active layer may be smaller than the absolute value of the LUMO of this metal oxide. The average size of the nanoparticles may be 1 nm or more, e.g., 1.5 nm or more, 2 nm or more, 2.5 nm or more, or 3 nm or more, and may be 10 nm or less, 9 nm or less, 8 nm or less, 7 nm or less, 6 nm or less, or 5 nm or less.

[0264] The hole blocking layer (HBL) may comprise, for example, at least one selected from 1,4,5,8-naphthalene-tetracarboxylic dianhydride (NTCDA), vasocuproin (BCP), tris[3-(3-pyridyl)-methityl]borane (3TPYMB), LiF, Alq3, Gaq3, Inq3, Znq2, Zn(BTZ)2, BeBq2, and combinations thereof, but is not limited thereto.

[0265] Each of the electron auxiliary layers (14) (e.g., electron injection layer, electron transport layer, or hole blocking layer) may have a thickness of 5 nm or more, 6 nm or more, 7 nm or more, 8 nm or more, 9 nm or more, 10 nm or more, 11 nm or more, 12 nm or more, 13 nm or more, 14 nm or more, 15 nm or more, 16 nm or more, 17 nm or more, 18 nm or more, 19 nm or more, or 20 nm or more, and may be 120 nm or less, 110 nm or less, 100 nm or less, 90 nm or less, 80 nm or less, 70 nm or less, 60 nm or less, 50 nm or less, 40 nm or less, 30 nm or less, or 25 nm or less, but is not limited thereto.

[0266] Referring to FIG. 6b, an electroluminescent device according to one embodiment may have a normal structure. The electroluminescent device (200) may include an anode (10) disposed on a transparent substrate (100) and a cathode (50) facing the anode (10). The anode (10) may include a transparent electrode based on a metal oxide, and the cathode (50) facing the anode (10) may include a conductive metal having a low work function. For example, the anode (positive electrode) may be an indium tin oxide (ITO, work function of about 4.6 eV to 5.1 eV) electrode, and the cathode (negative electrode) (50) may be an electrode comprising magnesium (Mg, work function of about 3.66 eV), aluminum (Al, work function of about 4.28 eV), or a combination thereof. Additionally, a hole auxiliary layer (20) may be disposed between the anode (10) and the quantum dot active layer (30). The hole auxiliary layer (20) may include a hole injection layer and / or a hole transport layer, and the hole injection layer may be disposed close to the anode (10), and the hole transport layer may be disposed close to the quantum dot active layer. Additionally, an electron auxiliary layer (40) may be disposed between the quantum dot active layer (30) and the cathode (50). The electron auxiliary layer (40) may include an electron injection layer and / or an electron transport layer, and the electron injection layer may be disposed close to the cathode (50), and the electron transport layer may be disposed close to the quantum dot active layer (30).

[0267] Referring to FIG. 6c, an electroluminescent device of another embodiment may have an inverted structure. An electroluminescent device (300) of an inverted structure may include a cathode (50) disposed on a transparent substrate (100) and an anode (10) facing the cathode (50). The cathode (50) may include a transparent electrode based on a metal oxide, and the anode (10) facing the cathode (50) may include a conductive metal having a high work function. For example, the anode (50) may be an indium tin oxide (ITO, work function of about 4.6 eV to 5.1 eV) electrode, and the cathode (10) may be an electrode comprising gold (Au, work function of about 5.1 eV), silver (Ag, work function of about 4.26 eV), aluminum (Al, work function of 4.28 eV), or a combination thereof. Additionally, an electronic auxiliary layer (40) may be disposed between the quantum dot active layer (30) and the cathode (50). The electronic auxiliary layer (40) may include an electron injection layer and / or an electron transport layer, and the electron injection layer may be disposed close to the cathode (50), and the electron transport layer may be disposed close to the quantum dot active layer (30). For example, the electron transport layer of the electronic auxiliary layer (40) may include a metal oxide, such as a crystalline Zn oxide or an n-type doped metal oxide. Additionally, a hole auxiliary layer (20) may be disposed between the anode (10) and the quantum dot active layer (30). The hole auxiliary layer (20) may include a hole injection layer and / or a hole transport layer, and the hole injection layer may be disposed close to the anode (10), and the hole transport layer may be disposed close to the quantum dot active layer (30). The hole transport layer may include TFB, PVK, or a combination thereof, and the hole injection layer may include MoO3 or other p-type metal oxides.

[0268] In an electroluminescent device, light of a certain wavelength generated in an active layer (30) is emitted to the outside through a light-transmitting electrode and a transparent substrate. For example, referring to FIG. 2, when a metal oxide-based transparent electrode (e.g., indium tin oxide (ITO)) is applied as a light-transmitting electrode to the anode (10), light formed in the active layer is emitted to the outside through the anode (10) and the transparent substrate (100). Referring to FIG. 3, when a metal oxide-based transparent electrode (e.g., indium tin oxide (ITO)) is applied as a light-transmitting electrode to the cathode (50), light formed in the active layer is emitted to the outside through the cathode (50) and the transparent substrate (100).

[0269] The aforementioned electronic device can be manufactured by a suitable method. For example, an electroluminescent device can be manufactured by forming a hole assist layer (or electron assist layer) on a substrate on which an electrode is formed, forming an active layer containing quantum dots (e.g., a pattern of the aforementioned quantum dots), and forming an electron assist layer (or hole assist layer) and an electrode on the active layer. The electrode, the hole assist layer, and the electron assist layer can each be formed independently by a suitable method, and may be formed, for example, by deposition or coating, but are not particularly limited.

[0270] Specific embodiments are presented below. However, the embodiments described below are merely for the purpose of specifically illustrating or explaining the invention and should not limit the scope of the invention.

[0271] [Example]

[0272] Analysis method

[0273] [1] Photoluminescence analysis

[0274] Hitachi F-7000 The photoluminescence (PL) spectrum of the fabricated nanocrystal is obtained using a spectrometer.

[0275] [2] UV Spectroscopic Analysis

[0276] UV spectroscopic analysis is performed using an Agilent Cary 5000 spectrometer, and the UV-Visible absorption spectrum is obtained.

[0277] [3] ICP analysis

[0278] Inductively coupled plasma atomic emission spectroscopy (ICP-AES) is performed using the Shimadzu ICPS-8100.

[0279] [4] X-ray photoelectron spectroscopy (XPS)

[0280] XPS analysis is performed using X-ray photoelectron spectroscopy (Manufacturer: Physical Electronics, Model: Quantum2000).

[0281] [5] TEM-EDX analysis

[0282] TEM-EDX analysis (element mapping) is performed using a UT F30 Tecnai electron microscope.

[0283] Example 1:

[0284] [1] Selenium and tellurium are dispersed in trioctylphosphine (TOP) to obtain a 0.4 M Se / TOP stock solution and a 0.5 M Te / TOP stock solution. A mixture is prepared containing the Te / TOP stock solution, an organic ligand containing oleylamine, and lithium aluminum hydride.

[0285] 0.9 mmol of zinc acetate is dissolved in 1-octadecene with oleic acid in a 300 mL reaction flask and heated to 120°C under vacuum. After 1 hour, the atmosphere inside the reactor is switched to an inert gas and heated to 300°C. The Se / TOP stock solution and the mixture are injected into the heated reaction system to perform the core formation reaction. The core formation reaction time is set to a total of 2 minutes.

[0286] Cool the reaction system to room temperature, add acetone to form a precipitate, and centrifuge the precipitate to obtain ZnTe x Se 1-x A core (x = approximately 0.6, diameter approximately 3.2 nm) is obtained. The obtained core is dispersed in toluene.

[0287] A zinc precursor is further prepared by heating zinc acetate in trioctylamine in the presence of oleic acid.

[0288] Trioctylamine is added to a 300 mL reaction flask, along with a zinc precursor and dibutyl magnesium. The resulting mixture is heated to 120°C under vacuum. After 1 hour, the atmosphere inside the reactor is switched to an inert gas. While heating the reaction system to a shell-forming temperature (above 250°C), the ZnTeSe core synthesized above, the Se / TOP stock solution, and optionally a zinc precursor are injected, and the reaction is carried out to form a magnesium-containing ZnSe shell (Zn(Mg)Se) on the core, thereby synthesizing ZnTeSe / Zn(Mg)Se quantum dots.

[0289] Prepare a 1 M S / TOP stock solution by dispersing sulfur in (TOP), and optionally add it to the reaction mixture along with a zinc precursor.

[0290] After the reaction is complete, the reaction system is cooled to room temperature, acetone is added to form a precipitate, and the precipitate is centrifuged to obtain ZnTeSe / Zn(Mg)Se / ZnS quantum dots. The obtained quantum dots are dispersed in toluene.

[0291] The (average) size of the synthesized quantum dots is approximately 5.5 nm.

[0292] [2] Analysis

[0293] XPS analysis was performed on the synthesized quantum dots, and the results are summarized in Table 1. TEM-EDX analysis was performed on the synthesized quantum dots, and a portion of the results is shown in Figure 7.

[0294] Atomic concentration (atom %) division Mg S Zn Se Te Example 1 0.93 1.27 3.84 0.83 1.08

[0295] XPS analysis results showed that Mg (Mg 2p or Mg 1s) could be detected in the synthesized quantum dots, and the Mg / Zn ratio in the atomic composition was confirmed to be approximately 0.24. No peaks related to Mg metal or MgO were detected. Example 2:

[0296] A ZnTeSe core dispersion is prepared in the same way as in Example 1.

[0297] A zinc precursor is prepared by heating zinc acetate in trioctylamine in the presence of oleic acid. Sulfur is dispersed in trioctylphosphine (TOP) to obtain a 1 M S / TOP stock solution.

[0298] Trioctylamine is added to a 250 mL reaction flask, and a zinc precursor and dibutyl magnesium are added. The resulting mixture is heated to 120°C under vacuum. After 15 minutes to 1 hour, the atmosphere inside the reactor is switched to an inert gas. While heating the reaction system to the shell-forming temperature (above 250°C), the ZnTeSe core synthesized above, the Se / TOP stock solution, and optionally the zinc precursor are injected, and the reaction is carried out to form a magnesium-containing ZnSe shell on the core. Subsequently, the S / TOP stock solution is injected along with the zinc precursor, and the reaction is carried out to form a ZnS shell layer.

[0299] The total reaction time is set to approximately 100 minutes.

[0300] After the reaction is complete, the reaction system is cooled to room temperature, acetone is added to form a precipitate, and the precipitate is centrifuged to obtain ZnTeSe / Zn(Mg)Se / ZnS quantum dots. The obtained quantum dots are dispersed in toluene.

[0301] In the shell formation step, the amount of Se and S used for the separated core is adjusted to obtain the desired quantum dot composition as shown in Table 2.

[0302] The (average) size of the manufactured quantum dots is approximately 5.34 nm.

[0303] Photoluminescence spectroscopic analysis was performed on the synthesized quantum dots, and the results are shown in Table 2. ICP analysis was performed on the synthesized quantum dots, and the results are shown in Table 2.

[0304] Comparative Example 1:

[0305] ZnTeSe / ZnSe / ZnS quantum dots are obtained in the same manner as in Example 2, except that a magnesium precursor is not used.

[0306] Photoluminescence spectroscopic analysis was performed on the synthesized quantum dots, and the results are shown in Table 2. ICP analysis was performed on the synthesized quantum dots, and the results are shown in Table 2.

[0307] Example 3:

[0308] A ZnTeSe core dispersion is prepared in the same way as in Example 1.

[0309] ZnTeSe / Zn(Mg)Se / Zn(Mg)S quantum dots are obtained in virtually the same manner as in Example 2, except that a magnesium precursor is added during ZnS shell formation and the shell composition is controlled as shown in Table 2 below. The (average) size of the prepared quantum dots is approximately 5.72 nm.

[0311] Photoluminescence spectroscopic analysis was performed on the synthesized quantum dots, and the results are shown in Table 2. ICP analysis was performed on the synthesized quantum dots, and the results are shown in Table 2.

[0312] ICP-AES (mole) PL wavelength and wavelength shift (relative value) S Zn Se Te Mg Example 2 6.64 16.89 3.00 1 3.286 542 nm (85%) Comparative Example 1 12.67 20.71 2.83 1 - 550 nm (100%) Example 3 7.88 14.18 2.09 1 3.424 528 nm (55%)

[0313] From the table above, it is confirmed that the quantum dots of the examples can significantly suppress the red shift phenomenon compared to the quantum dots of the comparative examples. Example 4:

[0314] A ZnTeSe core dispersion is prepared in the same way as in Example 1.

[0315] ZnTeSe / Zn(Mg)Se / ZnS quantum dots are obtained in virtually the same manner as in Example 2, except that the shell composition is adjusted as shown in Table 3 below.

[0316] UV-Vis absorption spectroscopy and photoluminescence spectroscopy were performed on the synthesized quantum dots, and the results are shown in Table 3. ICP analysis was performed on the synthesized quantum dots, and the results are shown in Table 3.

[0317] The (average) size of the manufactured quantum dots is approximately 4.43 nm.

[0318] Comparative Example 2:

[0319] ZnTeSe / ZnSe / ZnS quantum dots are obtained in the same way as in Example 4, except that a magnesium precursor is not used.

[0320] Photoluminescence spectroscopic analysis was performed on the synthesized quantum dots, and the results are shown in Table 3. ICP analysis was performed on the synthesized quantum dots, and the results are shown in Table 3.

[0321] ICP-AES properties Optical properties S Zn Se Te Mg Wavelength Shift QY(FWHM) VD Example 4 0.55 8.98 4.00 1 5.614 19 nm 72.8%(36nm) 0.1 Comparative Example 2 0.56 8.03 2.67 1 - 29 nm Approximately 44.1% (38 nm) 0.02

[0322] Wavelength shift: Shift value relative to core PL wavelength QY: Quantum efficiency,

[0323] FWHM: Half width

[0324] VD: valley depth

[0325] The results of Table 3 suggest that the quantum dots of the examples can exhibit improved optical properties compared to the comparative examples.

[0326] Although the embodiments have been described in detail above, the scope of the rights is not limited thereto, and various modifications and improvements by those skilled in the art using the basic concepts defined in the following claims also fall within the scope of the rights of the present invention.

Claims

Claim 1 A quantum dot comprising zinc, tellurium, and selenium, wherein the quantum dot comprises a core comprising a first zinc chalcogenide comprising zinc, tellurium, and selenium, and a semiconductor nanocrystal shell disposed on the core comprising a second zinc chalcogenide, wherein the quantum dot further comprises magnesium, wherein the molar ratio of tellurium to selenium in the quantum dot is greater than 0.1, wherein the quantum dot has a quantum efficiency of 60% or more, wherein the molar ratio of magnesium to tellurium in the quantum dot is 0.6 or more and 10 or less, and wherein the quantum dot does not comprise cadmium. Claim 2 In claim 1, the quantum dot is configured to emit green light. Claim 3 In claim 1, the semiconductor nanocrystal shell comprises a first layer disposed on the core and a second layer disposed on the first layer, wherein the first layer comprises a second semiconductor nanocrystal and the second layer comprises a third semiconductor nanocrystal having a composition different from that of the second semiconductor nanocrystal, wherein the second semiconductor nanocrystal comprises zinc and selenium and does not comprise sulfur, and the third semiconductor nanocrystal comprises zinc and sulfur and does not comprise selenium, and at least one of the second semiconductor nanocrystal and the third semiconductor nanocrystal further comprises magnesium. Claim 4 In claim 1, the quantum dot has a molar ratio of tellurium to selenium (Te / Se) of 0.15 or more and 4 or less, and a molar ratio of magnesium to tellurium of 2 or more and 8 or less. Claim 5 In claim 1, the quantum dots wherein the molar ratio of magnesium to tellurium is 1 or more and 9 or less. Claim 6 In claim 1, the quantum dot comprises magnesium at the interface between the core, the semiconductor nanocrystal shell, or the core and the semiconductor nanocrystal shell. Claim 7 In claim 1, the quantum dot further comprises an additional metal including an alkali metal, aluminum, or a combination thereof. Claim 8 In claim 7, the quantum dot has a molar ratio of the additional metal to tellurium of 0.001 or more. Claim 9 In claim 1, the quantum dot is a quantum dot that does not include indium phosphide, gallium phosphide, or a combination thereof. Claim 10 In paragraph 2, the green light is a quantum dot having a maximum emission peak in the range of 480 nm or more and 560 nm or less. Claim 11 In claim 1, the maximum emission peak of the quantum dot is a quantum dot having a full width at half maximum of 45 nm or less. Claim 12 In claim 1, the quantum dot is a quantum dot having a quantum efficiency of 65% or more. Claim 13 In claim 1, the quantum dots are quantum dots having a size of 4.5 nm or more and 7 nm or less. Claim 14 The quantum dot of claim 1 further comprises sulfur, wherein the molar ratio of sulfur to selenium in the quantum dot is 0.1 or higher, the molar ratio of the total of sulfur and selenium to tellurium is less than 15, the molar ratio of tellurium to selenium is 4:1 or lower, the molar ratio of sulfur to zinc is 0.95 or lower, or the molar ratio of tellurium to sulfur is greater than 0.

12. Claim 15 In claim 1, the semiconductor nanocrystal shell comprises a first layer disposed on the core and a second layer disposed on the first layer, wherein the first layer comprises a second semiconductor nanocrystal and the second layer comprises a third semiconductor nanocrystal having a composition different from that of the second semiconductor nanocrystal, wherein the second semiconductor nanocrystal comprises zinc, selenium, and optionally sulfur, and the third semiconductor nanocrystal comprises zinc and sulfur, and at least one of the second semiconductor nanocrystal and the third semiconductor nanocrystal further comprises magnesium. Claim 16 In claim 1, the semiconductor nanocrystal shell comprises a first layer disposed on the core and a second layer disposed on the first layer, wherein the first layer comprises a second semiconductor nanocrystal and the second layer comprises a third semiconductor nanocrystal having a composition different from that of the second semiconductor nanocrystal, and the second semiconductor nanocrystal comprises zinc selenide, magnesium selenide, or a combination thereof, or the third semiconductor nanocrystal comprises zinc sulfide, magnesium sulfide, or a combination thereof. Claim 17 In claim 1, the quantum dot comprises an organic ligand, wherein the organic ligand comprises RCOOH, RNH2, R2NH, R3N, RSH, RH2PO, R2HPO, R3PO, RH2P, R2HP, R3P, ROH, RCOOR', RPO(OH)2, RHPOOH, R2POOH (wherein R and R' are each independently a substituted or unsubstituted C1 to C40 aliphatic hydrocarbon, or a substituted or unsubstituted C6 to C40 aromatic hydrocarbon), a polymer organic ligand, or a combination thereof. Claim 18 A method for manufacturing a quantum dot according to claim 1, comprising the steps of: preparing a particle including the core; and reacting a zinc precursor and a chalcogen element precursor at a shell-forming temperature in an organic solvent in the presence of the core particle and an organic ligand to form the semiconductor nanocrystal shell on the surface of the core particle, wherein at least one of the steps of preparing the core particle and forming the semiconductor nanocrystal shell includes adding a magnesium precursor to the reaction system. Claim 19 In claim 18, the method wherein the magnesium precursor comprises magnesium carboxylate, magnesium alkylate, or a combination thereof. Claim 20 A quantum dot complex comprising a matrix; and a plurality of quantum dots dispersed within the matrix, wherein the plurality of quantum dots include the quantum dots of claim 1. Claim 21 A display element comprising a light-emitting element, wherein the light-emitting element comprises a quantum dot of claim 1. Claim 22 An electronic device comprising a first electrode and a second electrode facing each other, and an active layer located between the first electrode and the second electrode and including the quantum dot of claim 1.

Citation Information

Patent Citations

  • Semiconductor nanocrystal

    KR1020110140049A

  • Quantum dot films, lighting devices, and lighting methods

    KR1020130120486A

  • Shell structures for colloidal semiconductor nanocrystals

    WO2020132245A1

  • Quantum dots and devices including the same

    KR1020180013801A